Addressing Bias in Non‐Probability Fisheries Surveys Using Multilevel Regression and Poststratification Approaches - Zachary Radford; Wendy Edwards; Samantha Hook; Bridgid Bell; Rebecca Mills; Grace Farrell; Martin J. Genner; Stephen D. Simpson; Kieran Hyder (Fish and Fisheries, 2026)
Quantifying harvest of fish stocks is challenging as census data are often unavailable, so surveys are required. Traditional probability‐based surveys use random sampling to obtain representative data that can be scaled to estimate total impact. However, these surveys are costly, so cheaper, non‐probability, citizen science surveys of self‐selected participants are becoming commonplace. Respondents in these surveys may not be representative and inclusion probabilities are unknown, making weighting difficult. This resembles exit polls, which successfully predict election outcomes using Multi‐level Regression and Post‐stratification (MRP), but this has not been tested in fisheries. This study applied MRP to quantify UK recreational sea angling (RSA) participation and catches using data from the UK Sea Angling Diary Project. This represents a ‘worst‐case’ scenario, as there is no sampling frame and no mandatory reporting. Five Bayesian multi‐level models were fitted to two survey datasets: one quantifying participation and days fished, and another location, numbers, and weight of fish caught. Predictions were post‐stratified using UK census data. Estimates from the traditional reweighting and MRP were compared, and a simulation approach was used to assess the accuracy and precision of the two methods. MRP reduced self‐selection bias and improved estimates in under‐represented groups, producing a 40% and 61% improvement for participation and catch, respectively. Average annual UK RSA participation was estimated to be 688,000 anglers, with 6.1 million days fished. Annual catch estimates were 32.4 million fish, weighing 14,876 t. This study demonstrates the value of MRP for reducing bias when analysing and scaling non‐probabilistically collected survey data.

Corrigendum to ’changing Pseudo-nitzschia and Dinophysis distributions in the North Sea and Western approaches (NE Atlantic) and their potential use in biodiversity assessments’ [harmful algae 156 (2026) 103113] - Matthew M. Holland; Eileen Bresnan; Martin Edwards; Matthew Faith; Clare Ostle; Rowena Stern; Paul Tett; Claire Widdicombe; Callum Whyte; Abigail McQuatters-Gollop (Harmful Algae, 2026)

Climate sensitivity and glacial inception in the European Alps across marine isotope stage 11 and 10 - Alexandre Honiat; Jonathan L. Baker; Gina E. Moseley; Martin Trüssel; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Changing Pseudo-nitzschia and Dinophysis distributions in the North Sea and Western Approaches (NE Atlantic) and their potential use in biodiversity assessments - Matthew M Holland; Eileen Bresnan; Martin Edwards; Matthew Faith; Clare Ostle; Rowena Stern; Paul Tett; Claire Widdicombe; Callum Whyte; Abigail McQuatters-Gollop (Harmful Algae, 2026)

Lung function and inflammation in healthy young adults after 6.6 hours of 0.07 ppm ozone exposure - Edward R. Pennington; Jairus C. Pulczinski; Martin W. Case; Jacob S. Griffin; Neil E. Alexis; Ilona Jaspers; Carole Robinette; Ann Chelminski; Andrea Davis; Neena Miller; David B. Peden; Andrew J. Ghio; et al. (Environmental Research, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Fall Armyworm (Spodoptera Frugiperda) Management and Baby Corn Yield Under Organic, Conventional, and Integrated Farming Systems in Sub-humid Tropics - Martin Muriuki; Felix Matheri; David Bautze; Edward Karanja; Anne Kelly Kambura; Edwin Mwangi; Nancy Munyoki; Chrysantus Tanga; Milka Kiboi (Journal of Crop Health, 2026)

Why controlling for habitat amount is critical for resolving the fragmentation debate - Lenore Fahrig; Carmen Galán‐Acedo; Brandon P. M. Edwards; Andrew K. Habrich; Amanda E. Martin; Cécile H. Albert; Victor Arroyo‐Rodríguez; Allison D. Binley; Jonathan R. Cole; Jessica K. Lockhart; Scott E. Nielsen; Federico Riva; et al. (Conservation Biology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Cracking the crust: Rifting and lateral magma transport at the early Holocene Sveinar-Randarhólar Fissure, NE Iceland - Adam Abersteiner; Christoph Beier; Sæmundur A. Halldórsson; Edward W. Marshall; Eemu Ranta; Magnús Á. Sigurgeirsson; Martin Whitehouse; Heejin Jeon (Journal of Volcanology and Geothermal Research, 2026)

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Comparing Effectiveness of Experimental and Implemented Bycatch Reduction Measures: the Ideal and the Real - Ray Hilborn; Eric Gilman; Martin Hall; C. Tara Marshall; Edward Melvin; Maite Pons (Reviews in Fisheries Science & Aquaculture, 2026)

Organic farming with smallholder input rates cannot close the yield gap in Central Kenya - David Bautze; Anouk Unternährer; Felix Matheri; Martin Muriuki; Edward Karanja; Milka Kiboi (Organic Agriculture, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Patterns of plastic occurrence during the pre- and post-Super Typhoon Rai (Odette) event in Olango Island Wildlife Sanctuary (OIWS), Philippines - Apple AJ D. Langcamon; Maria Kristina O. Paler; Emiko Fujita; Yutaka Kameda; Mark Edward M. Walton; Martin W. Skov; Jan G. Hiddink; Evelyn B. Taboada (Marine Pollution Bulletin, 2026)

Are mangrove ecosystems plastic accumulation zones? - Shaira Kyle M. Tagalog; Maria Kristina O. Paler; Mark Edward M. Walton; Martin W. Skov; Jan G. Hiddink; Evelyn B. Taboada (Science of The Total Environment, 2026)

Hydroxyl (OH) radical oxidation of surfactant films formed from woodland aerosol particulate material at the air-water interface - Edward J. Stuckey; Rebecca J.L. Welbourn; Tobias W.D. Robson; Connor R. Barker; Matthew Wilkinson; James I.L. Morison; Martin D. King (Atmospheric Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Challenging the conductive paradigm: The unexpected role of sand in anaerobic digestion - Nicolás Hoffmann; Cátia S.N. Braga; Olga Rubilar; Gustavo Ciudad; Gonzalo Tortella; Edward Hermosilla; M.Salomé Duarte; Luciana Pereira; Andreia F. Salvador; Gilberto Martins (Bioresource Technology, 2025)

Repeatability of diffusion and perfusion MRI derived radiomic features in glioblastoma: a test-retest study - Philip Martin; Lois Holloway; Peter Metcalfe; Eng-Siew Koh; Farhannah Aly; Edward Chan; Caterina Brighi (Physical and Engineering Sciences in Medicine, 2025)

Linking crystal shape and dynamic undercooling: a new framework for inferring magmatic crystallization histories - Amanda Lindoo; Madeleine C. S. Humphreys; Charlotte Gordon; Martin F. Mangler; Edward W. Llewellin; Richard A. Brooker; Fabian B. Wadsworth; Eshbal Geifman (Contributions to Mineralogy and Petrology, 2025)
Magmas contain crystals exhibiting diverse shapes and sizes, yet the relationship between crystal shape (specifically aspect ratio) and undercooling ( $$Δ T$$ ), the driving force for crystallization, remains poorly constrained. Crystal shape should correlate with undercooling because undercooling governs the growth regime (interface-controlled versus diffusion-controlled) and thus the resulting crystal form. Prior experiments confirm that large nominal undercoolings drive transitions from polyhedral to hopper, skeletal, or dendritic forms. Large undercoolings reflect rapid decompression or cooling, differing from slower cooling rates typical of magmatic intrusions and storage systems. In such slowly cooled environments, crystals remain polyhedral, exhibiting subtle shape variations. Accurately quantifying crystal shape evolution at relatively low undercoolings could provide critical insights into crystallization histories, improving interpretations of the timescales and processes governing magma storage and eruption dynamics. Experimental verification of correlations between aspect ratios of polyhedral crystals and cooling rates remains inconclusive, possibly because nominal undercooling neglects the dynamic evolution of undercooling throughout crystallization. To address this, we introduce average instantaneous undercooling ( $$\overline{{Δ T_{I} }}$$ ), a metric capturing dynamic undercooling history during crystallization. Through controlled cooling experiments and numerical modelling, we demonstrate that higher $$\overline{{Δ T_{I} }}$$ histories produce tabular, high aspect ratio plagioclase crystals, whereas lower $$\overline{{Δ T_{I} }}$$ produces more prismatic crystals with lower aspect ratios. These variations in shape reflect undercooling-driven shifts in the predominant growth mechanism operating on different crystal faces. By quantitatively linking crystal shape to $$\overline{{Δ T_{I} }}$$ , our study provides a new approach for reconstructing crystallization histories in magmas under varying pH2O-T-t conditions.

Children’s multi-dimensional accessibility to urban green infrastructure: A systematic review of assessment methods and outlook - Ahmadreza Irajpour; Francesc Baró; Martin Edwards; Sareh Moosavi; Emilie Lacroix; Maider Llaguno-Munitxa (Urban Forestry & Urban Greening, 2025)

A systemically applied nanoparticle-based dsRNA biopesticide reduces Tuta absoluta survival - William T. Askew; Angharad M.R. Gatehouse; Martin G. Edwards (Pesticide Biochemistry and Physiology, 2025)

Voltammetric fingerprinting of aqueous infusion of chemically modified yerba mate leaves: ASCA model analysis and PLS-DA discrimination - Mayara Martins Fonseca; Gustavo Galo Marcheafave; Bruna Coldibeli; Ivar Wendling; Roy Edward Bruns; Elen Romão Sartori (Food Chemistry, 2025)

Earliest trace fossil evidence of wood-eating termites (Isoptera) and mites (Oribatida) in circumpolar environments of Australia - Juliana Edwards; Anthony J. Martin; William M.G. Parker; Melissa Lowery; Ankit Dodla; Magdalena Giergiel; Callum Gassner; Bayden R. Wood; Thomas H. Rich; Alistair R. Evans; Patricia Vickers-Rich (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Sustainable management of non-timber forest products in Peruvian Amazonia: lessons learnt from participatory use of smartphone technology - Charlotte E. Wheeler; Althea L. Davies; Luis Andueza; Lydia E.S. Cole; Nállarett Dávila; Jhon Del Águila; Margarita del Aguila Villacorta; Frederick C. Draper; Charlotte L.D. Evans; Eurídice N. Honorio Coronado; Nina Laurie; Eva Loja; et al. (Journal of Environmental Management, 2025)

An economical and rapid method of comet assay and micronucleus cytome assay for genotoxicity biomonitoring using clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Edward Inpent Campal; Shubra Singh; Nalini Poojary; Martin Xavier; Kiran D. Rasal; Madhuri S. Pathak; Naresh S. Nagpure (DNA Repair, 2025)

Environmental, neuropsychological, and physiological factors in urban outdoor thermal comfort assessments: a systematic review - Pranav Pandya; Maider Llaguno-Munitxa; Martin Gareth Edwards; Emilie Lacroix; Gabriele Manoli; Ariane Middel (International Journal of Biometeorology, 2025)

Remdesivir is active in vitro against tick-borne encephalitis virus and selects for resistance mutations in the viral RNA-dependent RNA polymerase - Kristina Nyström; Edward Trybala; Joanna Said; Anette Roth; Marianela Patzi Churqui; Ambjörn Kärmander; Tomas Cihlar; John P. Bilello; Tomas Bergström; Martin Lagging (Infectious Diseases, 2025)

Comparison of NO2 diffusion tube measurement methods and related uncertainties - David Medland; Gabriel Garcia; Tom Gardiner; Nicholas A. Martin; Valerio Ferracci; Ashley Wilkins; David Fryer; Tom Holmes; Pete Edwards; Sebastian Diez; David Butterfield (Atmospheric Environment, 2025)

Interactive effects of crop types and nitrogen sources on N2O emissions in a cool humid climate - Joannie D’Amours; David E. Pelster; Martin H. Chantigny; Andrew C. VanderZaag; Erin L. Smith; Gilles Bélanger; Émilie Maillard; Marie-Élise Samson; Edward G. Gregorich; Denis A. Angers; Isabelle Royer; Marie-Noëlle Thivierge (Plant and Soil, 2025)
Aims Perennial forages in rotation with annual crops can improve agricultural resilience by increasing soil organic carbon. However, how nitrogen (N) sources interact with rotation diversity to influence soil nitrous oxide (N 2 O) emissions is not well understood. Methods During three snow-free seasons, N 2 O emissions, crop yields, and ancillary variables were measured at three experimental sites with contrasting soil textures (silty clay and sandy loam) in eastern Canada. Using a split-plot design, we compared a corn ( Zea mays L.)-soybean ( Glycine max [L.] Merr.)-corn rotation and a mixed perennial grass sward receiving N via: i) mineral fertilizer (MIN), ii) liquid dairy manure (LDM), and iii) inclusion of alfalfa ( Medicago sativa L.) to the perennial forages with no additional N (LEG). Results When summed across sites over all three years, cumulative N 2 O emissions were greater for LDM than MIN in annual crops (8.75 ± 1.63 and 5.15 ± 0.96 kg N 2 O-N ha –1 , respectively), but not in perennial grasses (2.95 ± 0.55 and 3.76 ± 0.70 kg N 2 O-N ha –1 , respectively). When comparing N sources within each crop type over the three years, MIN generated greater yields than LDM in annual and perennial crops, but lower yield-scaled N 2 O emissions than LDM in annual crops only. During forages post-seeding years, area- and yield-scaled N 2 O emissions induced by LDM and LEG were lower than MIN. Conclusion Our results suggest that for a cool humid climate using LDM or LEG in perennial forages and MIN on annual crops can reduce overall N 2 O emissions, while generating similar or lower yield-scaled emissions.

On the limit: Estimating round baler torque for grass harvesting scenarios - Tomás Crotty; John Warren; Conor Shanahan; Edward Jones; Martin Glavin; Dallan Byrne (Computers and Electronics in Agriculture, 2025)

The variability of the topside ionospheres of Venus and Mars as seen by recent radio science observations - Kerstin Peter; Martin Pätzold; Paul Withers; Robin Ramstad; Edward Thiemann; Markus Fränz; Silvia Tellmann; Bernd Häusler; Yoshifumi Futaana; Mats Holmström (Icarus, 2025)

Data-Driven Closure Parametrizations with Metrics: Dispersive Transport - Edward Coltman; Martin Schneider; Rainer Helmig (Transport in Porous Media, 2025)
This work presents a data-driven framework for multi-scale parametrization of velocity-dependent dispersive transport in porous media. Pore-scale flow and transport simulations are conducted on periodic pore geometries, and volume averaging is used to isolate dispersive transport, producing parameters for the dispersive closure term at the representative elementary volume scale. After validation on unit cells with symmetric and asymmetric geometries, a convolutional neural network is trained to predict dispersivity directly from pore geometry images. Descriptive metrics are also introduced to better understand the parameter space and are used to build a neural network that predicts dispersivity based solely on these metrics. While the models predict longitudinal dispersivity well, transversal dispersivity remains difficult to capture, likely requiring more advanced models to fully describe pore-scale transversal dynamics.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

IFN-γ/IL-2 Double-Color FluoroSpot Assay for Monitoring Human Primary T Cell Activation: Validation, Inter-Laboratory Comparison, and Recommendations for Clinical Studies - Alexandra Mauthe; Edward Cedrone; Raquel Villar-Hernández; Elisa Rusch; Marco Springer; Martin Schuster; Rosemarie Preyer; Marina A. Dobrovolskaia; Matthias Gutekunst (The AAPS Journal, 2025)
The enzyme-linked immunosorbent spot (EliSpot) assay and its fluorescence-based version, FluoroSpot, are sensitive immunoassays commonly used to quantify antigen-specific T and B lymphocytes and other immune cells in peripheral blood or homogenized tissues. Due to their high sensitivity, these assays are popular in clinical trials to evaluate the efficacy of immunotherapy and vaccines, which involve a high level of scrutiny to ensure valid study results. Besides industry consensus white papers and other research publications, there is no formal guidance for the industry on how to validate EliSpot and FluoroSpot assays to ensure their accurate performance for immune monitoring in clinical trials. Herein, we describe a comprehensive in vitro study using healthy human donor peripheral blood mononuclear cells (PBMCs) and model antigens to validate a double-color FluoroSpot assay for monitoring antigen-specific lymphocytes by detecting and quantifying IFN-γ and IL-2-producing lymphocytes. Validation parameters, acceptance criteria set-up, and assay limits—limit of detection (LOD), minimum positive control response, lower and upper limits of quantification (LLOQ and ULOQ)—were determined, and assay performance was demonstrated by assessing precision, specificity, linearity, and robustness. In addition, an inter-laboratory comparison demonstrated concordance between assay results from two laboratories. In summary, this study outlines a robust approach to EliSpot and FluoroSpot validation and demonstrates that the IFN-γ/IL-2 FluoroSpot assay is suitable for the reliable detection of antigen-specific immune responses from PBMC samples across laboratories and meets the current regulatory requirements for bioanalytical method validation. Graphical Abstract

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Corrigendum to “Incorporating heterogeneity in farmer disease control behaviour into a livestock disease transmission model” Preventive Vet. Med. 219 (2023) 106019 - Edward M. Hill; Naomi S. Prosser; Paul E. Brown; Eamonn Ferguson; Martin J. Green; Jasmeet Kaler; Matt J. Keeling; Michael J. Tildesley (Preventive Veterinary Medicine, 2025)

Carbon recovery in secondary forests: Insights from three West African countries - Paly N. Titenwi; Moses N. Sainge; Usif Kargbo; Richard A.S. Kamara; Alex Musa; Timothy M. Kabba; Bockarie K. Buanie; Andre L. Njouonkou; Edward Aruna; Martin J.P. Sullivan; Ana Leite; Aida Cuni-Sanchez (Forest Ecology and Management, 2025)

Revisiting the sustainability science research agenda - Mesfin Sahle; Shruti Ashish Lahoti; So-Young Lee; Katja Brundiers; Carena J. van Riper; Christian Pohl; Herlin Chien; Iris C. Bohnet; Noé Aguilar-Rivera; Peter Edwards; Prajal Pradhan; Tobias Plieninger; et al. (Sustainability Science, 2025)

Representing biodiversity decline data by manipulating familiar audio files to create emotional responses: A novel sonification method of soundwave-level deletion - Edward J. Martin; Thomas R. Meagher; Daniel Barker (Biological Conservation, 2024)

Mature fruits of Gliricidia sepium and Leucaena leucocephala plants have potential as inexpensive protein and mineral supplements for ruminants - Andell Edwards; Victor Mlambo; Caven M. Mnisi; Martin P. Hughes (Agroforestry Systems, 2024)

Dynamic response of essential amino acid biosynthesis in Buchnera aphidicola to supplement sub-optimal host nutrition - Chloe C. Start; Catriona M.H. Anderson; Angharad M.R. Gatehouse; Martin G. Edwards (Journal of Insect Physiology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mutagenesis on a complex mouse genetic background by site-specific nucleases - Benjamin Davies; Lucy Trelfa; Victoria S. Rashbrook; Edward Drydale; Rachel Martin; Boyan Bai; Jedrzej Golebka; Daniel Stephen Biggs; Keith M. Channon; Shoumo Bhattacharya; Gillian Douglas (Transgenic Research, 2024)
Mouse models with complex genetic backgrounds are increasingly used in preclinical research to accurately model human disease and to enable temporal and cell-specific evaluation of genetic manipulations. Backcrossing mice onto these complex genetic backgrounds takes time and leads to significant wastage of animals. In this study, we aimed to evaluate whether site-specific nucleases could be used to generate additional genetic mutations in a complex genetic background, using the REVERSA mouse model of atherosclerosis, a model harbouring four genetically altered alleles. The model is comprised of a functional null mutation in the Ldlr gene in combination with a ApoB100 allele, which, after high-fat diet, leads to the rapid development of atherosclerosis. The regression of the pathology is achieved by inducible knock-out of the Mttp gene. Here we report an investigation to establish if microinjection of site-specific nucleases directly into zygotes prepared from the REVERSA could be used to investigate the role of the ATP binding cassette transporter G1 (ABCG1) in atherosclerosis regression. We show that using this approach we could successfully generate two independent knockout lines on the REVERSA background, both of which exhibited the expected phenotype of a significant reduction in cholesterol efflux to HDL in bone marrow-derived macrophages. However, loss of Abcg1 did not impact atherosclerosis regression in either the aortic root or in aortic arch, demonstrating no important role for this transporter subtype. We have demonstrated that site-specific nucleases can be used to create genetic modifications directly onto complex disease backgrounds and can be used to explore gene function without the need for laborious backcrossing of independent strains, conveying a significant 3Rs advantage.

RNAi targeting Na and CPR via leaf delivery reduces adult emergence and increases the susceptibility to λ-cyholthin in Tuta absoluta (Meyrick) - Yong-Qiang Li; Anqi Huang; Xiao-Jie Li; Martin G. Edwards; Angharad M.R. Gatehouse (Pesticide Biochemistry and Physiology, 2024)

Evaluating infectious disease outbreak potential and mitigation effectiveness on cruise ships - Rahele Mosleh; Mortaza Baky-Haskuee; Abbas Ghasemi; Martin Grunnill; Julien Arino; Mohammadali Tofighi; Edward W. Thommes; Jianhong Wu (Journal of Theoretical Biology, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Electrotrawling can improve the sustainability of the bottom trawl fishery for sole: a review of the evidence - Adriaan D. Rijnsdorp; Pim G. Boute; Justin C. Tiano; Dick de Haan; Marloes Kraan; Hans Polet; Edward Schram; Maarten Soetaert; Nathalie A. Steins; Martin Lankheet; Karline Soetaert (Reviews in Fish Biology and Fisheries, 2024)
Between 2009 and 2021 almost the complete beam trawl fleet of the Netherlands switched from conventional beam trawls (BT) to pulse trawls (PT) using electrical stimulation to catch sole, Solea solea . Electric fishing, being banned in the EU in 1988, was made possible in 2006 under a derogation. Over the years stakeholders expressed concern about ecosystem effects. Here we review the research conducted. PT improved the selectivity of the fishery and reduced the ecological side effects. PT caught more sole per hour fishing but less discards and benthos than BT. The transition to PT reduced the surface area swept (lower towing speed), sediment depth of disturbance and associated benthic impacts, as well as fuel consumption. Laboratory experiments with 9 fish and 17 benthic invertebrate species showed that exposure to a commercial bipolar pulse stimulus did not result in harmful effects except in cod. Autopsy of cod sampled from PT revealed that 40% had an internal injury. Injury rates in other roundfish species was low (< 2%) and absent in flatfish. Electrical-induced impacts on biogeochemistry were not observed. The transition increased competition with other fishers which fed the resentment against PT. Governance arrangements under which the number of temporary licenses expanded, undermined legitimacy of the gear, resulting in a ban in 2021. Although questions about the ecological impact of electrical stimulation remain, adverse effects are considered negligible in comparison with the benefits.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Detrending tree-ring widths in closed-canopy forests for climate and disturbance history reconstructions - Daniel L. Druckenbrod; Edward R. Cook; Neil Pederson; Dario Martin-Benito (Dendrochronologia, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Ocean climate and hydrodynamics drive decadal shifts in Northeast Atlantic dinoflagellates - Loïck Kléparski; Grégory Beaugrand; Clare Ostle; Martin Edwards; Morten D. Skogen; Nicolas Djeghri; Hjálmar Hátún (Global Change Biology, 2024)
The abundance of large marine dinoflagellates has declined in the North Sea since 1958. Although hypotheses have been proposed to explain this diminution (increasing temperature and wind), the mechanisms behind this pattern have thus far remained elusive. In this article, we study the long‐term changes in dinoflagellate biomass and biodiversity in relation to hydro‐climatic conditions and circulation within the North Atlantic. Our results show that the decline in biomass has paralleled an increase in biodiversity caused by a temperature‐induced northward movement of subtropical taxa along the European shelf‐edge, and facilitated by changes in oceanic circulation (subpolar gyre contraction). However, major changes in North Atlantic hydrodynamics in the 2010s (subpolar gyre expansion and low‐salinity anomaly) stopped this movement, which triggered a biodiversity collapse in the North Sea. Further, North Sea dinoflagellate biomass remained low because of warming. Our results, therefore, reveal that regional climate warming and changes in oceanic circulation strongly influenced shifts in dinoflagellate biomass and biodiversity.

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Organic and conventional farming systems shape soil bacterial community composition in tropical arable farming - Hans-Martin Krause; Joe G. Ono-Raphel; Edward Karanja; Felix Matheri; Martina Lori; Yina Cifuentes; Stefanie P. Glaeser; Andreas Gattinger; Amritbir Riar; Noah Adamtey; Paul Mäder (Applied Soil Ecology, 2023)

Incorporating heterogeneity in farmer disease control behaviour into a livestock disease transmission model - Edward M. Hill; Naomi S. Prosser; Paul E. Brown; Eamonn Ferguson; Martin J. Green; Jasmeet Kaler; Matt J. Keeling; Michael J. Tildesley (Preventive Veterinary Medicine, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Beach erosion aggravates the drastic decline in marine turtle populations in French Guiana - Damien Chevallier; Marc Girondot; Christina Péron; Jordan Martin; Marc Bonola; Johan Chevalier; Benoît de Thoisy; Laurent Kelle; Yvon Le Maho; Antoine Gardel; Edward J. Anthony (Regional Environmental Change, 2023)
Yalimapo beach, near the Maroni River estuary in French Guiana, is an important turtle nesting site. The interaction of massive mud banks migrating alongshore from the distant Amazon River with discharge from the Maroni River generates strong beach morpho-sedimentary changes. The eventual degradation of the marine turtle nesting habitats resulting from these changes represents a threat to the offspring, and consequently, to the turtle population. Field operator counts of green and leatherback turtle nests were combined with high-resolution topographic measurements of the beach over four field surveys in 2012 and 2014 to map the topographic modifications susceptible to affect nesting on Yalimapo beach. We assumed that the survival of nests was at stake when the depth of sand between the egg chamber and the topographic surface (i.e. the top) of the beach was < 50 cm, and that beach surface lowering > 10 cm represented unfavourable conditions for nest safety with unequal nest survival across the beach. Erosion of the beach surface exceeding a depth of 50 cm therefore results in nest destruction. Digital elevation models were produced to quantify the topographic modification of nesting on Yalimapo beach and highlight the endangered nesting areas. As the modification of the beach is not linear, some sectors are more eroded than others, resulting in unequal nest survival across the beach. Overall, up to 40% of the nests were presumed destroyed over the 2 years of survey, but true losses would depend on the species and the preferential locations of their nesting habitats. The relatively unfavourable conditions that prevailed during the 2 years of the survey are consistent with persistent erosion of Yalimpao beach since 2011. This ongoing erosion could explain in part the drastic decline of the leatherback turtle population in western French Guiana over the period 2001–2018. The substrate quality and dynamics of the nesting beach in relation to the preferred nesting habitat of each species are therefore critical issues that should be considered in the conservation strategies of marine turtles. The beach nesting conditions of marine turtles in French Guiana, as elsewhere, could be further aggravated in the future by climate change effects, including sea-level rise.

A massive Critically Endangered cloud forest tree, Microcos rumpi (Grewiaceae) new to science from the Rumpi Hills, SW Region, Cameroon - Martin Cheek; Sara Edwards; Jean Michel Onana (Kew Bulletin, 2023)
Summary We describe Microcos rumpi (Grewiaceae) a massive new species to science from the Rumpi Hills of SW Region Cameroon, a proposed Tropical Important Plant Area. Confined on current evidence to submontane forest, the species is threatened by expanding habitat clearance for farms and is assessed as Critically Endangered. A large tree, attaining 35 – 40 m height, and 80 cm trunk diam. at 1.3 m above ground, its biomass is calculated as in the range of 7 – 8 metric tonnes. It is the third tree species of the genus recorded from Cameroon and only the fourth recorded west of D.R. Congo. A key to these four species is presented. The concept of Microcos in Africa in relation to Grewia is discussed, and three new combinations are made, transferring three species names from Grewia to Microcos : Microcos louisii (R.Wilczek) Cheek, M. evrardii (R.Wilczek) Cheek and M. schmitzii (R.Wilczek) Cheek.

Antibiotic resistance genes in food production systems support One Health opinions - James M. Tiedje; Yuhao Fu; Zhi Mei; Andreas Schäffer; Qingyuan Dou; Wulf Amelung; Martin Elsner; Joseph Adu-Gyamfi; Lee Heng; Marko Virta; Xin Jiang; Hauke Smidt; et al. (Current Opinion in Environmental Science & Health, 2023)

Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Andre Rodrigues; Andrew J. Johnson; Ross A. Joseph; You Li; Nemat O. Keyhani; Edward L. Stanley; Benjamin Weiss; Martin Kaltenpoth; Matthew E. Smith; Jiri Hulcr (Symbiosis, 2023)

Phytoplankton life strategies, phenological shifts and climate change in the North Atlantic Ocean from 1850 to 2100 - Loïck Kléparski; Grégory Beaugrand; Martin Edwards; Clare Ostle (Global Change Biology, 2023)
Significant phenological shifts induced by climate change are projected within the phytoplankton community. However, projections from current Earth System Models (ESMs) understandably rely on simplified community responses that do not consider evolutionary strategies manifested as various phenotypes and trait groups. Here, we use a species‐based modelling approach, combined with large‐scale plankton observations, to investigate past, contemporary and future phenological shifts in diatoms (grouped by their morphological traits) and dinoflagellates in three key areas of the North Atlantic Ocean (North Sea, North‐East Atlantic and Labrador Sea) from 1850 to 2100. Our study reveals that the three phytoplanktonic groups exhibit coherent and different shifts in phenology and abundance throughout the North Atlantic Ocean. The seasonal duration of large flattened (i.e. oblate) diatoms is predicted to shrink and their abundance to decline, whereas the phenology of slow‐sinking elongated (i.e. prolate) diatoms and of dinoflagellates is expected to expand and their abundance to rise, which may alter carbon export in this important sink region. The increase in prolates and dinoflagellates, two groups currently not considered in ESMs, may alleviate the negative influence of global climate change on oblates, which are responsible of massive peaks of biomass and carbon export in spring. We suggest that including prolates and dinoflagellates in models may improve our understanding of the influence of global climate change on the biological carbon cycle in the oceans.

Corrigendum to “A functional size-spectrum model of the global marine ecosystem that resolves zooplankton composition”, Ecological Modelling, 2020, 435: 109265 - Ryan F. Heneghan; Jason D. Everett; Patrick Sykes; Sonia D. Batten; Martin Edwards; Kunio Takahashi; Iain M. Suthers; Julia L. Blanchard; Anthony J. Richardson (Ecological Modelling, 2023)

Immobilization effects of co-pyrolyzed neem seed mixed with poultry manure on potentially toxic elements in soil and the phytoremediation potentials of native Manihot esculenta and Jatropha curcas in ensuring sustainable land use - Martin Kofi Mensah; Carsten Drebenstedt; Ibukun Momoriola Ola; Nils Hoth; Frederick Gyasi Damptey; Edward Debrah Wiafe (Environmental Monitoring and Assessment, 2023)
This study evaluated the effects of neem seed biochar, poultry manure, and their combinations at varying rates of 15 and 25% (w/w) on potentially toxic elements (PTEs) in soils. Afterward, the suitability of Manihot esculenta and Jatropha curcas in removing Cd, As, Zn, Pb, and Hg from mine spoils were appraised in a 270-day outdoor pot experiment. Using ICP–Mass Spectrometry, the elemental contents of target PTE in the shoot, root, and soil specimens were determined for each treatment. The obtained average values were further subjected to a nonparametric test of samples using IBM SPSS Statistic 29. The applied organic amendments resulted in significant differences p < 0.05 in PTE availability for plant uptake after the Independent-Samples Kruskal–Wallis Test was made. Nonetheless, applying a 25% (w/w) mixture of neem seed biochar and poultry manure was efficient in immobilizing more PTEs in soils which caused lower PTEs presence in plants. Organic amendments further significantly enhanced the fertility of the mine soils leading to about a 6– 25.00% increase in the biomass yield ( p < 0.05) of both plants. No significant difference ( p > 0.05) was however observed between the phytoremediation potentials of both plants after the Independent-Sample Mann–Whitney U test. Even that, Manihot esculenta was averagely more efficient in PTE uptake than Jatropha curcas . Larger portions of the bioaccumulated PTEs were stored in the roots of both plants leading to high bioconcentration factors of 1.94– 2.47 mg/kg and 1.27– 4.70 mg/kg, respectively, for Jatropha curcas and Manihot esculenta. A transfer factor < 1 was achieved for all PTEs uptake by both plants and indicated their suitability for phytostabilization . Techniques for easy cultivation of root-storing PTEs are required to enhance their large-scale use as their biomass could further be used in clean energy production.

Tonian–Ediacaran evolution of the Brunovistulian microcontinent (Czech Republic) deciphered from LA-ICP-MS U–Pb zircon and 40Ar/39Ar muscovite ages - Martin J. Timmerman; Lukáš Krmíček; Simona Krmíčková; Jiří Sláma; Masafumi Sudo; Edward Sobel (Precambrian Research, 2023)

Biotinylation of reducing and non-reducing termini to create plug-and-play polysaccharides - Nimisha Mohandas; Patrick J.B. Edwards; Lisa M. Kent; Geoffrey B. Jameson; Martin A.K. Williams (Carbohydrate Polymers, 2023)

Evaluation of a long-term information tool reveals continued suitability for identifying bycatch hotspots but little effect on fisher location choice - Zachary A. Siders; Robert N.M. Ahrens; Summer Martin; Edward V. Camp; Alexander R. Gaos; John H. Wang; Jamie Marchetti; T. Todd Jones (Biological Conservation, 2023)

Composition and Patterns of Taxa Assemblages in the Western Channel Assessed by 18S Sequencing, Microscopy and Flow Cytometry - Rowena Stern; Kathryn Picard; Jessica Clarke; Charlotte E. Walker; Claudia Martins; Clare Marshall; Ana Amorim; E. Malcolm S. Woodward; Claire Widdicombe; Glen Tarran; Martin Edwards (Journal of Marine Science and Engineering, 2023)
Plankton monitoring by microscopy offers a long-term ecological perspective of plankton communities, but detection approaches are uniquely biased. Genetic identification of marine plankton has become standard but is still not used in routine monitoring. This study assesses the value that genetic methods bring to microscopic and flow cytometry monitoring methods in the Western (English) Channel. An 18S high throughput sequencing (HTS) diversity survey of plankton taxa was performed on samples collected from an automated Water and Microplankton Sampler (WaMS) deployed on the Continuous Plankton Recorder platform (CPR) from 2011–2012. This survey detected contrasting but complementary taxa assemblages to that of microscopic surveys, mostly composed of smaller or naked or thin-walled plankton taxa, with most phytoplankton being under 10 µm infrequently recorded by other surveys. Most genetically-detected taxa in the survey were mixotrophic or heterotrophic. In comparison with microscopic phytoplankton counts from the CPR survey and Western Channel Observatory station L4, only 8–12 taxonomic families were common to all three surveys, most of them dinoflagellates, with a bias towards larger diatoms and dinoflagellate taxa in microscopy surveys. Additional quantitative real-time PCR detection of two potentially harmful taxa, the pelagophyte, Aureococcus anophagefferens and four Pseudo-nitzschia from 2011–2013. This revealed that growth of A. anophagefferens was elevated in the summer of 2011, whilst the appearance of Pseudo-nitzschia delicatissima in February of that year contrasted with it’s timing at a coastal station. Smaller phytoplankton measured by flow cytometry had distinct seasonality and abundance in the mid-Atlantic compared to coastal regions reflecting distinct conditions.

Bioaccessibility of iron in pearl millet flour contaminated with different soil types - Molly Muleya; Scott D. Young; Martin R. Broadley; Edward J.M. Joy; Prosper Chopera; Elizabeth H. Bailey (Food Chemistry, 2023)

Artisanal gold mine spoil types within a common geological area and their variations in contaminant loads and human health risks - Martin Kofi Mensah; Carsten Drebenstedt; Nils Hoth; Ibukun Momoriola Ola; Precious Uchenna Okoroafor; Edward Debrah Wiafe (Environmental Monitoring and Assessment, 2023)
This study answered the question of whether mine spoils occurring in a common geological location had similarities in their contaminant load and associated health risks. Using inductively coupled plasma mass spectrometry, the total contents of Cd, Pb, As, Hg, Zn, Fe, and Al were determined for 110 digested soil samples obtained from underground rock ore (URS), oxide ore (OXS), and alluvial ore (AVS) mine spoils. Independent sample Kruskal–Wallis test and pairwise comparisons of sources were used to ascertain the variation in elemental load between the mine spoil investigated. The results showed that mine spoil contaminations and their ecological and health risk significantly varied ( p < 0.01) from each other and fell in the order OXS > URS > AVS > forest soils because of their geochemistry. Determined enrichment and geo-accumulation indices revealed that OXS and URS sites were severely–extremely polluted with Cd, Hg, and As, while AVS mine spoils were only moderately contaminated by Cd and As contents. Children had the highest tendency for developing noncarcinogenic health defects largely due to toxic contents of As, Cd, and Hg in soil materials near them than adult men and women would after obtaining a hazard index of 73.5 and 67.7 (unitless) at both OXS and URS sites. Mine spoils especially where hard rocks and oxide ores were processed are not fit for agricultural use or human habitation. The restriction of human access and sustainable remediation approaches are required to avert health defects. Even so, area-specific potentially toxic elements must be targeted during soil cleaning due to the significant variations in contaminant load between mined sites.

Inconclusive evidence that breathing shapes pupil dynamics in humans: a systematic review - Martin Schaefer; Sylvia Edwards; Frans Nordén; Johan N. Lundström; Artin Arshamian (Pflügers Archiv - European Journal of Physiology, 2023)
More than 50 years ago, it was proposed that breathing shapes pupil dynamics. This widespread idea is also the general understanding currently. However, there has been no attempt at synthesizing the progress on this topic since. We therefore conducted a systematic review of the literature on how breathing affects pupil dynamics in humans. We assessed the effect of breathing phase, depth, rate, and route (nose/mouth). We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and conducted a systematic search of the scientific literature databases MEDLINE, Web of Science, and PsycInfo in November 2021. Thirty-one studies were included in the final analyses, and their quality was assessed with QualSyst. The study findings were summarized in a descriptive manner, and the strength of the evidence for each parameter was estimated following the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. The effect of breathing phase on pupil dynamics was rated as “low” (6 studies). The effect of breathing depth and breathing rate (6 and 20 studies respectively) were rated as “very low”. Breathing route was not investigated by any of the included studies. Overall, we show that there is, at best, inconclusive evidence for an effect of breathing on pupil dynamics in humans. Finally, we suggest some possible confounders to be considered, and outstanding questions that need to be addressed, to answer this fundamental question. Trial registration: This systematic review has been registered in the international prospective register of systematic reviews (PROSPERO) under the registration number: CRD42022285044.

Fisheries Oceanography : The first 30 years and new challenges in the 21st century - Steven J. Bograd; Martin Edwards; Shin‐ichi Ito; Janet Nye; Emily Chappell (Fisheries Oceanography, 2023)
The journal Fisheries Oceanography provides a global forum for fisheries scientists and oceanographers to understand how marine ecosystems, and the services they provide to society, are structured and shaped by environmental variability and climate change. With this special issue, as well as the 30th Anniversary Virtual Issue of the most influential papers from the journal's history, we commemorate 30 years of publishing leading research in the field of fisheries oceanography. These issues showcase the extent, depth and impact of the research published in Fisheries Oceanography . We also reflect on the evolution of research themes through the journal's history, and highlight key emergent themes in our field. We look forward to continuing to publish impactful research in the pages of Fisheries Oceanography in the years ahead.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Krill biomass estimation: Sampling and measurement variability - Fiona Bairstow; Sven Gastauer; Simon Wotherspoon; C. Tom A. Brown; So Kawaguchi; Tom Edwards; Martin J. Cox (Frontiers in Marine Science, 2022)
Krill are the subject of growing commercial fisheries and therefore fisheries management is necessary to ensure long-term sustainability. Krill catch limits, set by Commission for the Conservation of Antarctic Marine Living Resources, are based on absolute krill biomass, estimated from acoustic-trawl surveys. In this work, we develop a method for determining an error budget for acoustic-trawl surveys of krill which includes sampling and measurement variability. We use our error budget method to examine the sensitivity of biomass estimates to parameters in acoustic target strength (TS) models, length frequency distribution and length to wetmass relationships derived from net data. We determined that the average coefficient of variation ( CV ) of estimated biomass was 17.7% and the average CV due from scaling acoustic observations to biomass density was 5.3%. We found that a large proportion of the variability of biomass estimates is due to the krill orientation distribution, a parameter in the TS model. Orientation distributions with narrow standard deviations were found to emphasise the results of nulls in the TS to length relationship, which has to potential to lead to biologically implausible results.

Global insights on managing fishery systems for the three pillars of sustainability - Taryn Garlock; James L. Anderson; Frank Asche; Martin D. Smith; Edward Camp; Jingjie Chu; Kai Lorenzen; Stefania Vannuccini (Fish and Fisheries, 2022)
There is growing recognition that fisheries should be managed for all three pillars of sustainability: economic, social and environmental sustainability. Limited quantitative evidence exists on factors supporting social sustainability, much less factors that contribute to multiple dimensions of sustainability. To develop a broader understanding of the factors that influence the performance of fishery management systems in environmental, economic and social pillars, we examine 11 input factors conjectured to contribute to successful fisheries using a global dataset of 145 fisheries case studies. The analysis indicates that management approaches are cross‐cutting and contribute to multiple dimensions of sustainability to varying extents. Importantly, factors exogenous to fisheries management can be as important as fisheries management, suggesting collaboration of fisheries institutions with other public and private institutions is important for sustainable fisheries development.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Saltmarsh Resilience to Periodic Shifts in Tidal Channels - Cai John Tomos Ladd; Mollie Frances Duggan-Edwards; Jordi F. Pagès; Martin Wiggers Skov (Frontiers in Marine Science, 2021)
Resilience of coastal ecosystems to climate change is largely determined by the interaction between plants and the surrounding tidal environment. Research has tended to focus on processes operating at the local scale to explain resilience mechanisms, overlooking potentially important landscape-scale processes and patterns. We show from aerial images spanning 67 years across 3 estuaries that saltmarsh loss was compensated by expansion elsewhere in the estuary when tidal channels shifted position. Compensatory expansion rates were as high as 6 m/yr. This phenomenon of “geomorphic compensation” represents a hitherto overlooked large-scale self-organizing pattern that facilitates the long-term persistence of marshes in estuaries. The geomorphic compensation pattern likely also occurs in other hydrological systems including mangrove forests, and seagrass meadows, and river islands. Compensatory erosion-expansion patterns occurred at the same time as net marsh extent increased by between 120 and 235% across all three estuaries. Marsh expansion mostly occurred in the lower parts of each estuary, where channel migration and compensatory expansion was less evident. Patterns of geomorphic compensation therefore appear to operate at discrete spatio-temporal scales, nested within a hierarchy of coastal morphodynamic processes that govern longer-term patterns of either net marsh gain or loss. Coastal ecosystem resilience can therefore only be fully appreciated when examining erosion and expansion patterns at both local and landscape scales. The intrinsic dynamics of marshes described here have important implications for the long-term delivery of ecosystem services.

Corrigendum: Seasonal and Ontogenetic Variation in Depth Use by a Critically Endangered Benthic Elasmobranch and Its Implications for Spatial Management - James Thorburn; Peter J. Wright; Edward Lavender; Jane Dodd; Francis Neat; Julien G. A. Martin; Caroline Lynam; Mark James (Frontiers in Marine Science, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Seasonal and Ontogenetic Variation in Depth Use by a Critically Endangered Benthic Elasmobranch and Its Implications for Spatial Management - James Thorburn; Peter J. Wright; Edward Lavender; Jane Dodd; Francis Neat; Julien G. A. Martin; Caroline Lynam; Mark James (Frontiers in Marine Science, 2021)
Seasonal and ontogenetic variations in depth use by benthic species are often concomitant with changes in their spatial distribution. This has implications for the efficacy of spatial conservation measures such as marine protected areas (MPAs). The critically endangered flapper skate ( Dipturus intermedius ) is the designation feature of an MPA in Scotland. This species is generally associated with deeper waters >100 m; however, little is known about its seasonal or ontogenetic variation in habitat use. This study used archival depth data from 25 immature and mature flapper skate tagged in the MPA over multiple years. Time series ranged from 3 to 772 (mean = 246) days. Generalised additive mixed models and highest density intervals were used to identify home (95%) and core (50%) highest density depth regions (HDDRs) to quantify depth use in relation to time of year and body size. Skate used a total depth range of 1–312 m, but home HDDRs typically occurred between 20 and 225 m. Core HDDRs displayed significant seasonal and ontogenetic variations. Summer core HDDRs (100–150 m) suggest high occupancy of the deep trenches in the region by skate of most size classes. There was an inverse relationship between body size and depth use and a seasonal trend of skate moving into shallow water over winter months. These results suggest that flapper skate are not solely associated with deep water, as skate, especially large females, are frequently found in shallow waters (25–75 m). The current management, which protects the entire depth range, is appropriate for the protection of flapper skate through much of its life history. This research demonstrates why collecting data across seasonal scales and multiple ontogenetic stages is needed to assess the effectiveness of spatial management.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Improving the Accuracy of Krill Target Strength Using a Shape Catalog - Fiona Bairstow; Sven Gastauer; Luke Finley; Tom Edwards; C. Tom A. Brown; So Kawaguchi; Martin J. Cox (Frontiers in Marine Science, 2021)
Antarctic krill are subject to precautionary catch limits, based on biomass estimates, to ensure human activities do not adversely impact their important ecological role. Accurate target strength models of individual krill underpin biomass estimates. These models are scaled using measured and estimated distributions of length and orientation. However, while the length distribution of a krill swarm is accessible from net samples, there is currently limited consensus on the method for estimating krill orientation distribution. This leads to a limiting factor in biomass calculations. In this work, we consider geometric shape as a variable in target strength calculations and describe a practical method for generating a catalog of krill shapes. A catalog of shapes produces a more variable target strength response than an equivalent population of a scaled generic shape. Furthermore, using a shape catalog has the greatest impact on backscattering cross-section (linearized target strength) where the dominant scattering mechanism is mie scattering, irrespective of orientation distribution weighting. We suggest that shape distributions should be used in addition to length and orientation distributions to improve the accuracy of krill biomass estimates.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Calc-alkaline volcanic rocks and zircon ages of the late Tonian: early Cryogenian arc-related Big Naryn Complex in the Eastern Djetim-Too Range, Middle Tianshan block, Kyrgyzstan - Baiansuluu Terbishalieva; Martin Jan Timmerman; Alexander Mikolaichuk; Uwe Altenberger; Jiří Sláma; Anja Maria Schleicher; Masafumi Sudo; Edward R. Sobel; Sarah B. Cichy (International Journal of Earth Sciences, 2021)
The Big Naryn Complex (BNC) in the East Djetim-Too Range of the Kyrgyz Middle Tianshan block is a tectonized, at least 2 km thick sequence of predominantly felsic to intermediate volcanic rocks intruded by porphyric rhyolite sills. It overlies a basement of metamorphic rocks and is overlain by late Neoproterozoic Djetim-Too Formation sediments; these also occur as tectonic intercalations in the BNC. The up to ca. 1100 m thick Lower Member is composed of predominantly rhyolites-to-dacites and minor basalts, while the at least 900 m thick pyroclastic Upper Member is dominated by rhyolitic-to-dacitic ignimbrites. Porphyric rhyolite sills are concentrated at the top of the Lower Member. A Lower Member rhyolite and a sill sample have LA-ICP-MS U–Pb zircon crystallization ages of 726.1 ± 2.2 Ma and 720.3 ± 6.5 Ma, respectively, showing that most of the magmatism occurred within a short time span in the late Tonian–early Cryogenian. Inherited zircons in the sill sample have Neoarchean (2.63, 2.64 Ga), Paleo- (2.33–1.81 Ga), Meso- (1.55 Ga), and Neoproterozoic (ca. 815 Ma) ages, and were derived from a heterogeneous Kuilyu Complex basement. A 1751 ± 7 Ma 40 Ar/ 39 Ar age for amphibole from metagabbro is the age of cooling subsequent to Paleoproterozoic metamorphism of the Kuilyu Complex. The large amount of pyroclastic rocks, and their major and trace element compositions, the presence of Neoarchean to Neoproterozoic inherited zircons and a depositional basement of metamorphic rocks point to formation of the BNC in a continental magmatic arc setting.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

A marine teleost, Opsanus beta, compensates acidosis in hypersaline water by H+ excretion or reduced HCO3− excretion rather than HCO3− uptake - Zongli Yao; Kevin L. Schauer; Ilan M. Ruhr; Edward M. Mager; Rachael M. Heuer; Martin Grosell (Journal of Comparative Physiology B, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Volatile Organic Compounds as Insect Repellents and Plant Elicitors: an Integrated Pest Management (IPM) Strategy for Glasshouse Whitefly (Trialeurodes vaporariorum) - Niall J.A. Conboy; Thomas McDaniel; David George; Adam Ormerod; Martin Edwards; Paul Donohoe; Angharad M. R Gatehouse; Colin R. Tosh (Journal of Chemical Ecology, 2020)
The glasshouse whitefly ( Trialeurodes vaporariorum Westwood) is a polyphagous arthropod pest that is of particular detriment to glasshouse grown tomato ( Solanum lycopersicum ) across temperate regions of the world. Control of whiteflies with synthetic pesticides has resulted in the evolution of resistant genotypes and a reduction in natural enemies, thus highlighting the need for environmentally sound control strategies. Volatile organic compounds (VOCs) offer an environmentally benign alternative to synthetic chemical sprays and this study explored the use of VOCs as insect repellents and plant defence elicitors to control whiteflies on tomato in a commercial glasshouse setting. Limonene in the form of a volatile dispenser system was found to successfully repel whitefly from the target crop and increased fruit yield by 32% during a heavy whitefly infestation. Analysis of tomato herbivore induced plant volatiles (HIPVs) led us to select methyl salicylate (MeSA) as the plant elicitor and application of MeSA to un-infested tomato plants was found to successfully reduce whitefly population development and increase yield by 11%, although this difference was marginally statistically significant. Combination of these two methods was also effective but whitefly abundance in combined plots was similar to the standalone limonene treatment across the course of the experiment. All of the VOC based control methods we used had a negative impact on whitefly performance, with more pronounced effects during the first few weeks of infestation. In subsequent laboratory experiments, we found elevated peroxidase (POD) activity and a significant increase in TPX1 and PR1 transcripts in MeSA treated plants. This led us to deduce that MeSA immediately induced plant defences, rather than priming them. We did however see evidence for residual priming, as plants treated with MeSA and infested with whiteflies produced significantly higher levels of POD activity than whitefly infestation alone. Despite the fact that our treatments failed to synergise, our methods can be optimised further, and the effectiveness of the standalone treatments is promising for future studies. In particular, our repellent limonene dispensers were extremely effective at deterring whiteflies and offer a low economic cost and easy to implement whitefly control option. The methods we have used here could be incorporated into current integrated pest management (IPM) systems, a sustainable approach to pest control which will be central to our efforts to manage whitefly populations under glass in the future.

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Significance of norovirus in occupational health: a review of published norovirus outbreaks in Central and Northern Europe - Felix Martin Hofmann; Edward Olawumi; Martina Michaelis; Ulrich Stößel; Friedrich Hofmann (International Archives of Occupational and Environmental Health, 2020)
Objectives Globally, norovirus (NoV) is the leading cause of gastroenteritis infection among all ages. The development of prevention strategies in the field of occupational health requires a detailed knowledge about the impact of the disease on employees. This review article aims not only at evaluating the burden of NoV outbreaks on staff but also at discussing implications for future prevention strategies. Methods Published NoV outbreaks in Central and Northern Europe were identified via a systematic literature search. Additionally, published NoV outbreaks in Germany were detected via a manual literature search. Key epidemiological data, as the number of symptomatic staff, was then extracted. The proportion of affected employees was calculated for each dataset (single NoV outbreaks or aggregated data of multiple outbreaks). Results Overall, 116 datasets were extracted from 72 relevant articles. 144,852 persons were affected by NoV gastroenteritis, 25,408 out of them (17.5%) were employees. 23,874 (94.0%) of them fell sick during outbreaks in hospitals and related settings. NoV cases among personnel in food establishments were reported only sporadically (mean ratio: 0.01). Conclusions Employees in hospitals and community facilities seem quantitatively to be most vulnerable towards NoV epidemics. Therefore, high quality of prevention measures in these settings, respective compliance with prevention strategies should have the highest priority. The disease can be considered as an occupational disease, even regularly without long-term consequences. Following work safety rules, a vaccination for vulnerable groups should be recommended if the vaccine development turns out to be successful.

Deforestation leakage undermines conservation value of tropical and subtropical forest protected areas - Scott Alan Ford; Martin Rudbeck Jepsen; Naomi Kingston; Edward Lewis; Thomas M. Brooks; Brian MacSharry; Ole Mertz (Global Ecology and Biogeography, 2020)
Aim The establishment of protected areas is among the most widespread responses to mitigate species loss. Although protected areas are often assumed to have conservation benefits, negative impacts have also been documented. One potential negative outcome is leakage, whereby protected areas displace land‐use activities harmful to conservation into adjacent areas. This can undermine protection by accelerating loss of species or skewing judgements of effectiveness. This study assessed the prevalence of deforestation leakage in a pan‐tropical and subtropical selection of 120 protected areas. Location Tropical and subtropical forest regions of America, Africa and Asia. Time period 2001–2017. Major taxa studied Threatened species of amphibians, birds and terrestrial mammals. Methods We used Global Forest Change data to assess the average yearly rate of deforestation in protected areas, protected area buffer zones and statistically matched, unprotected control areas. We calculated and compared irreplaceability of habitat for threatened amphibian, bird and terrestrial mammal species between protected areas and buffer zones. Results In 55 cases, deforestation rates were higher in buffer zones than in protected and control areas, suggesting a relatively high prevalence of deforestation leakage stemming from protected areas. In 78.2% of documented leakage cases, reduced deforestation in protected areas was not sufficient to offset the amount of deforestation in 10 km buffer zones to a level that would be expected without protection. In 90.9% of leakage cases, the irreplaceability of species in the 10 km buffer zone was greater than that of the protected area, implying a negative impact of leakage on threatened species. Main conclusions The results suggest that protected areas are generally effective at preventing deforestation within their jurisdiction; however, leakage patterns can undermine conservation success because buffer zones often contain habitat for threatened species. We recommend accounting for the possibility of leakage when designing new protected areas and networks.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

From cave geomorphology to Palaeolithic human behaviour: speleogenesis, palaeoenvironmental changes and archaeological insight in the Atxurra‐Armiña cave (northern Iberian Peninsula) - Martin Arriolabengoa; Inaki Intxaurbe; Mª Ángeles Medina‐Alcaide; Olivia Rivero; Joseba Rios‐Garaizar; Inaki LÍbano; Peru Bilbao; Arantza Aranburu; Hai Cheng; Richard Lawrence Edwards; Diego Garate (Journal of Quaternary Science, 2020)
A detailed geomorphological study was performed in the Atxurra‐Armiña cave system (northern Iberian Peninsula) to decode landscape evolution, palaeoenvironmental changes and human use of a cave within an Inner Archaeological Context. The results show an average incision rate of the river of –1 for at least the last 419 ka, with interruptions due to sedimentary inputs. Moreover, allostratigraphic units comprising fluviokarstic deposits at the base and flowstone formation at the top have been shown to be climatically controlled, formed either during glacial–interglacial cycles or during interstadial cycles. Finally, when the cave was used by humans in the Late Magdalenian, the lower entrance was closed, and they must therefore have entered the cave through the upper entrance. To reach the sectors selected to decorate the panels, they probably travelled from the upper cave level, as the current crawlway was wider than today, according to our U/Th dating. Once these visitors reached the panels, the floor in the main gallery would have been around 15 cm lower than at present. However, the morphology of the conduit was similar; this has significant implications for understanding and interpreting the human use of the cave during the Palaeolithic.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Targeting Cell Contractile Forces: A Novel Minimally Invasive Treatment Strategy for Fibrosis - Keerthi Atluri; Sathivel Chinnathambi; Alyssa Mendenhall; James A. Martin; Edward A. Sander; Aliasger K. Salem (Annals of Biomedical Engineering, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

The accuracy of volunteer surveyors for obtaining tree measurements in tropical forests - Barnabas Harrison; Thomas Edward Martin; Abdul Haris Mustari (Ambio, 2020)

A proteomic-based approach to study underlying molecular responses of the small intestine of Wistar rats to genetically modified corn (MON810) - Asmaa AL-Harbi; Sahira Lary; Martin G. Edwards; Safaa Qusti; Andrew Cockburn; Morten Poulsen; Angharad M. R. Gatehouse (Transgenic Research, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

What controls the extreme flow through the Kerama Gap: a global HYbrid Coordinate Ocean Model reanalysis point of view - Zhitao Yu; Edward J. Metzger; Harley E. Hurlburt; Ole Martin Smedstad (Ocean Dynamics, 2019)

An Integrated All-Atlantic Ocean Observing System in 2030 - Brad deYoung; Martin Visbeck; Moacyr Cunha de Araujo Filho; Molly O’Neil Baringer; CarolAnne Black; Erik Buch; Gabrielle Canonico; Paulo Coelho; Janice T. Duha; Martin Edwards; Albert Fischer; Jan-Stefan Fritz; et al. (Frontiers in Marine Science, 2019)

On Methodological issues in the Indo-European debate By Michel Danino - Marina Silva; John T Koch; Maria Pala; Ceiridwen J Edwards; Pedro Soares; Martin B Richards (Journal of Biosciences, 2019)

A Global Plankton Diversity Monitoring Program - Sonia D. Batten; Rana Abu-Alhaija; Sanae Chiba; Martin Edwards; George Graham; R. Jyothibabu; John A. Kitchener; Philippe Koubbi; Abigail McQuatters-Gollop; Erik Muxagata; Clare Ostle; Anthony J. Richardson; et al. (Frontiers in Marine Science, 2019)

Environmental risk assessment of antibiotics in agroecosystems: ecotoxicological effects on aquatic microbial communities and dissemination of antimicrobial resistances and antibiotic biodegradation potential along the soil-water continuum - Fabrice Martin-Laurent; Edward Topp; Loren Billet; Isabelle Batisson; Cédric Malandain; Pascale Besse-Hoggan; Soizic Morin; Joan Artigas; Chloé Bonnineau; Laura Kergoat; Marion Devers-Lamrani; Stéphane Pesce (Environmental Science and Pollution Research, 2019)

Intestinal nerve cell injury occurs prior to insulin resistance in female mice ingesting a high-fat diet - Yvonne Nyavor; Rachel Estill; Hannah Edwards; Hailey Ogden; Kaila Heideman; Kiefer Starks; Christopher Miller; George May; Lance Flesch; John McMillan; Martin Gericke; Larry Forney; et al. (Cell and Tissue Research, 2019)

Drainage enhances modern soil carbon contribution but reduces old soil carbon contribution to ecosystem respiration in tundra ecosystems - Min Jung Kwon; Susan M. Natali; Caitlin E. Hicks Pries; Edward A. G. Schuur; Axel Steinhof; K. Grace Crummer; Nikita Zimov; Sergey A. Zimov; Martin Heimann; Olaf Kolle; Mathias Göckede (Global Change Biology, 2019)
Warming temperatures are likely to accelerate permafrost thaw in the Arctic, potentially leading to the release of old carbon previously stored in deep frozen soil layers. Deeper thaw depths in combination with geomorphological changes due to the loss of ice structures in permafrost, may modify soil water distribution, creating wetter or drier soil conditions. Previous studies revealed higher ecosystem respiration rates under drier conditions, and this study investigated the cause of the increased ecosystem respiration rates using radiocarbon signatures of respired CO 2 from two drying manipulation experiments: one in moist and the other in wet tundra. We demonstrate that higher contributions of CO 2 from shallow soil layers (0–15 cm; modern soil carbon) drive the increased ecosystem respiration rates, while contributions from deeper soil (below 15 cm from surface and down to the permafrost table; old soil carbon) decreased. These changes can be attributed to more aerobic conditions in shallow soil layers, but also the soil temperature increases in shallow layers but decreases in deep layers, due to the altered thermal properties of organic soils. Decreased abundance of aerenchymatous plant species following drainage in wet tundra reduced old carbon release but increased aboveground plant biomass elevated contributions of autotrophic respiration to ecosystem respiration. The results of this study suggest that drier soils following drainage may accelerate decomposition of modern soil carbon in shallow layers but slow down decomposition of old soil carbon in deep layers, which may offset some of the old soil carbon loss from thawing permafrost.

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Pragmatic criteria to define chronic pseudomonas aeruginosa infection among adults with cystic fibrosis - Zhe Hui Hoo; Elizabeth Coates; Chin Maguire; Hannah Cantrill; Nadia Shafi; Edward F. Nash; Angela McGowan; Stephen J. Bourke; William G. Flight; Thomas V. Daniels; Julia A. Nightingale; Mark I. Allenby; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

OXI1 kinase plays a key role in resistance of Arabidopsis towards aphids (Myzus persicae) - Tahsin Shoala; Martin G. Edwards; Marc R. Knight; Angharad M. R. Gatehouse (Transgenic Research, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Prospects for seasonal forecasting of iceberg distributions in the North Atlantic - Robert Marsh; Grant Bigg; Yifan Zhao; Matthew J. Martin; Jeffrey R. Blundell; Simon A. Josey; Edward Hanna; Vladimir Ivchenko (Natural Hazards, 2018)

Displacement of a landslide retaining wall and application of an enhanced failure forecasting approach - Tommaso Carlà; Renato Macciotta; Michael Hendry; Derek Martin; Tom Edwards; Trevor Evans; Paolo Farina; Emanuele Intrieri; Nicola Casagli (Landslides, 2018)

Development of a rapid MALDI-TOF MS based epidemiological screening method using MRSA as a model organism - Åsa Lindgren; Nahid Karami; Roger Karlsson; Christina Åhrén; Martin Welker; Edward R. B. Moore; Liselott Svensson Stadler (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Oligomer-prone E57K-mutant alpha-synuclein exacerbates integration deficit of adult hippocampal newborn neurons in transgenic mice - Martin Regensburger; Sebastian R. Schreglmann; Svenja Stoll; Edward Rockenstein; Sandra Loskarn; Wei Xiang; Eliezer Masliah; Beate Winner (Brain Structure and Function, 2017)

Proteomic Expression Changes in Large Cerebral Arteries After Experimental Subarachnoid Hemorrhage in Rat Are Regulated by the MEK-ERK1/2 Pathway - Anne H. Müller; Alistair V.G. Edwards; Martin R. Larsen; Janne Nielsen; Karin Warfvinge; Gro K. Povlsen; Lars Edvinsson (Journal of Molecular Neuroscience, 2017)

Elemental composition of Malawian rice - Edward J. M. Joy; E. Louise Ander; Martin R. Broadley; Scott D. Young; Allan D. C. Chilimba; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2017)

Plants, microorganisms, and soil temperatures contribute to a decrease in methane fluxes on a drained Arctic floodplain - Min Jung Kwon; Felix Beulig; Iulia Ilie; Marcus Wildner; Kirsten Küsel; Lutz Merbold; Miguel D. Mahecha; Nikita Zimov; Sergey A. Zimov; Martin Heimann; Edward A. G. Schuur; Joel E. Kostka; et al. (Global Change Biology, 2017)
As surface temperatures are expected to rise in the future, ice‐rich permafrost may thaw, altering soil topography and hydrology and creating a mosaic of wet and dry soil surfaces in the Arctic. Arctic wetlands are large sources of CH 4 , and investigating effects of soil hydrology on CH 4 fluxes is of great importance for predicting ecosystem feedback in response to climate change. In this study, we investigate how a decade‐long drying manipulation on an Arctic floodplain influences CH 4 ‐associated microorganisms, soil thermal regimes, and plant communities. Moreover, we examine how these drainage‐induced changes may then modify CH 4 fluxes in the growing and nongrowing seasons. This study shows that drainage substantially lowered the abundance of methanogens along with methanotrophic bacteria, which may have reduced CH 4 cycling. Soil temperatures of the drained areas were lower in deep, anoxic soil layers (below 30 cm), but higher in oxic topsoil layers (0–15 cm) compared to the control wet areas. This pattern of soil temperatures may have reduced the rates of methanogenesis while elevating those of CH 4 oxidation, thereby decreasing net CH 4 fluxes. The abundance of Eriophorum angustifolium , an aerenchymatous plant species, diminished significantly in the drained areas. Due to this decrease, a higher fraction of CH 4 was alternatively emitted to the atmosphere by diffusion, possibly increasing the potential for CH 4 oxidation and leading to a decrease in net CH 4 fluxes compared to a control site. Drainage lowered CH 4 fluxes by a factor of 20 during the growing season, with postdrainage changes in microbial communities, soil temperatures, and plant communities also contributing to this reduction. In contrast, we observed CH 4 emissions increased by 10% in the drained areas during the nongrowing season, although this difference was insignificant given the small magnitudes of fluxes. This study showed that long‐term drainage considerably reduced CH 4 fluxes through modified ecosystem properties.

Current Trends in Ligand Binding Real-Time Measurement Technologies - Stephanie Fraser; Judy Y. Shih; Mark Ware; Edward O’Connor; Mark J. Cameron; Martin Schwickart; Xuemei Zhao; Karin Regnstrom (The AAPS Journal, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Alterations in the Cerebral Microvascular Proteome Expression Profile After Transient Global Cerebral Ischemia in Rat - Stine Spray; Sara E. Johansson; Alistair V. G. Edwards; Martin R. Larsen; Aneta Radziwon-Balicka; Gro K. Povlsen; Lars Edvinsson (Journal of Molecular Neuroscience, 2017)

Valuing increased zinc (Zn) fertiliser-use in Pakistan - Edward J. M. Joy; Waqar Ahmad; Munir H. Zia; Diriba B. Kumssa; Scott D. Young; E. Louise Ander; Michael J. Watts; Alexander J. Stein; Martin R. Broadley (Plant and Soil, 2017)

A high-density SNP genotyping array for Brassica napus and its ancestral diploid species based on optimised selection of single-locus markers in the allotetraploid genome - Wayne E. Clarke; Erin E. Higgins; Joerg Plieske; Ralf Wieseke; Christine Sidebottom; Yogendra Khedikar; Jacqueline Batley; Dave Edwards; Jinling Meng; Ruiyuan Li; Cynthia Taylor Lawley; Jérôme Pauquet; et al. (Theoretical and Applied Genetics, 2016)

Projections of climate change effects on discharge and inundation in the Amazon basin - Mino Viana Sorribas; Rodrigo C. D. Paiva; John M. Melack; Juan Martin Bravo; Charles Jones; Leila Carvalho; Edward Beighley; Bruce Forsberg; Marcos Heil Costa (Climatic Change, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Molecular mechanisms of D-cycloserine in facilitating fear extinction: insights from RNAseq - Stefanie Malan-Müller; Lorren Fairbairn; Willie M. U. Daniels; Mahjoubeh Jalali Sefid Dashti; Edward J. Oakeley; Marc Altorfer; Martin Kidd; Soraya Seedat; Junaid Gamieldien; Sîan Megan Joanna Hemmings (Metabolic Brain Disease, 2016)

Negative impacts of high temperatures on growth of black spruce forests intensify with the anticipated climate warming - Martin P. Girardin; Edward H. Hogg; Pierre Y. Bernier; Werner A. Kurz; Xiao Jing Guo; Guillaume Cyr (Global Change Biology, 2016)
An increasing number of studies conclude that water limitations and heat stress may hinder the capacity of black spruce ( Picea mariana (Mill.) B.S.P.) trees, a dominant species of Canada's boreal forests, to grow and assimilate atmospheric carbon. However, there is currently no scientific consensus on the future of these forests over the next century in the context of widespread climate warming. The large spatial extent of black spruce forests across the Canadian boreal forest and associated variability in climate, demography, and site conditions pose challenges for projecting future climate change responses. Here we provide an evaluation of the impacts of climate warming and drying, as well as increasing [CO 2 ], on the aboveground productivity of black spruce forests across Canada south of 60°N for the period 1971 to 2100. We use a new extensive network of tree‐ring data obtained from Canada's National Forest Inventory, spatially explicit simulations of net primary productivity (NPP) and its drivers, and multivariate statistical modeling. We found that soil water availability is a significant driver of black spruce interannual variability in productivity across broad areas of the western to eastern Canadian boreal forest. Interannual variability in productivity was also found to be driven by autotrophic respiration in the warmest regions. In most regions, the impacts of soil water availability and respiration on interannual variability in productivity occurred during the phase of carbohydrate accumulation the year preceding tree‐ring formation. Results from projections suggest an increase in the importance of soil water availability and respiration as limiting factors on NPP over the next century due to warming, but this response may vary to the extent that other factors such as carbon dioxide fertilization, and respiration acclimation to high temperature, contribute to dampening these limitations.

Blastocyst genotyping for quality control of mouse mutant archives: an ethical and economical approach - Ferdinando Scavizzi; Edward Ryder; Stuart Newman; Marcello Raspa; Diane Gleeson; Hannah Wardle-Jones; Lluis Montoliu; Almudena Fernandez; Marie-Laure Dessain; Vanessa Larrigaldie; Zuzana Khorshidi; Reetta Vuolteenaho; et al. (Transgenic Research, 2015)

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Females Exceed Males in Mercury Concentrations of Burbot Lota lota - Charles P. Madenjian; Martin A. Stapanian; Peter A. Cott; David P. Krabbenhoft; William H. Edwards; Lynn M. Ogilvie; Justin G. Mychek-Londer; John F. DeWild (Archives of Environmental Contamination and Toxicology, 2015)

Zinc-enriched fertilisers as a potential public health intervention in Africa - Edward J. M. Joy; Alexander J. Stein; Scott D. Young; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Expression of cytochrome P450 CYP81A6 in rice: tissue specificity, protein subcellular localization, and response to herbicide application - Hai-ping Lu; Martin Edwards; Qi-zhao Wang; Hai-jun Zhao; Hao-wei Fu; Jian-zhong Huang; Angharad Gatehouse; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2015)

Beak and feather disease viruses circulating in Cape parrots (Poicepahlus robustus) in South Africa - Guy L. Regnard; Rutledge S. Boyes; Rowan O. Martin; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2015)

Beak and feather disease virus: correlation between viral load and clinical signs in wild Cape parrots (Poicepahlus robustus) in South Africa - Guy L. Regnard; Rutledge S. Boyes; Rowan O. Martin; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2015)

Warming shelf seas drive the subtropicalization of European pelagic fish communities - Ignasi Montero‐Serra; Martin Edwards; Martin J. Genner (Global Change Biology, 2015)
Pelagic fishes are among the most ecologically and economically important fish species in European seas. In principle, these pelagic fishes have potential to demonstrate rapid abundance and distribution shifts in response to climatic variability due to their high adult motility, planktonic larval stages, and low dependence on benthic habitat for food or shelter during their life histories. Here, we provide evidence of substantial climate‐driven changes to the structure of pelagic fish communities in European shelf seas. We investigated the patterns of species‐level change using catch records from 57 870 fisheries‐independent survey trawls from across European continental shelf region between 1965 and 2012. We analysed changes in the distribution and rate of occurrence of the six most common species, and observed a strong subtropicalization of the North Sea and Baltic Sea assemblages. These areas have shifted away from cold‐water assemblages typically characterized by Atlantic herring and European sprat from the 1960s to 1980s, to warmer‐water assemblages including Atlantic mackerel, Atlantic horse mackerel, European pilchard and European anchovy from the 1990s onwards. We next investigated if warming sea temperatures have forced these changes using temporally comprehensive data from the North Sea region. Our models indicated the primary driver of change in these species has been sea surface temperatures in all cases. Together, these analyses highlight how individual species responses have combined to result in a dramatic subtropicalization of the pelagic fish assemblage of the European continental shelf.

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Solution Behavior and Crystallization of Cytochrome bc 1 in the Presence of Amphipols - Delphine Charvolin; Martin Picard; Li-Shar Huang; Edward A. Berry; Jean-Luc Popot (The Journal of Membrane Biology, 2014)

Next Generation Ligand Binding Assays—Review of Emerging Real-Time Measurement Technologies - Stephanie Fraser; Mark Cameron; Edward O’Connor; Martin Schwickart; Michael Tanen; Mark Ware (The AAPS Journal, 2014)

Multi‐decadal range changes vs. thermal adaptation for north east Atlantic oceanic copepods in the face of climate change - Stephanie L. Hinder; Mike B. Gravenor; Martin Edwards; Clare Ostle; Owen G. Bodger; Patricia L. M. Lee; Antony W. Walne; Graeme C. Hays (Global Change Biology, 2014)
Populations may potentially respond to climate change in various ways including moving to new areas or alternatively staying where they are and adapting as conditions shift. Traditional laboratory and mesocosm experiments last days to weeks and thus only give a limited picture of thermal adaptation, whereas ocean warming occurring over decades allows the potential for selection of new strains better adapted to warmer conditions. Evidence for adaptation in natural systems is equivocal. We used a 50‐year time series comprising of 117 056 samples in the NE Atlantic, to quantify the abundance and distribution of two particularly important and abundant members of the ocean plankton (copepods of the genus Calanus ) that play a key trophic role for fisheries. Abundance of C. finmarchicus , a cold‐water species, and C. helgolandicus , a warm‐water species, were negatively and positively related to sea surface temperature ( SST ) respectively. However, the abundance vs. SST relationships for neither species changed over time in a manner consistent with thermal adaptation. Accompanying the lack of evidence for thermal adaptation there has been an unabated range contraction for C. finmarchicus and range expansion for C. helgolandicus . Our evidence suggests that thermal adaptation has not mitigated the impacts of ocean warming for dramatic range changes of these key species and points to continued dramatic climate induced changes in the biology of the oceans.

A proteomic approach to study the mechanism of tolerance to Bt toxins in Ostrinia furnacalis larvae selected for resistance to Cry1Ab - Lina Xu; Natalie Ferry; Zhenying Wang; Jie Zhang; Martin G. Edwards; Angharad M. R. Gatehouse; Kanglai He (Transgenic Research, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Risk of dietary magnesium deficiency is low in most African countries based on food supply data - Edward J. M. Joy; Scott D. Young; Colin R. Black; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2013)

Estimating abundance while accounting for rarity, correlated behavior, and other sources of variation in counts - Robert M. Dorazio; Julien Martin; Holly H. Edwards (Ecology, 2013)
The class of N ‐mixture models allows abundance to be estimated from repeated, point count surveys while adjusting for imperfect detection of individuals. We developed an extension of N ‐mixture models to account for two commonly observed phenomena in point count surveys: rarity and lack of independence induced by unmeasurable sources of variation in the detectability of individuals. Rarity increases the number of locations with zero detections in excess of those expected under simple models of abundance (e.g., Poisson or negative binomial). Correlated behavior of individuals and other phenomena, though difficult to measure, increases the variation in detection probabilities among surveys. Our extension of N ‐mixture models includes a hurdle model of abundance and a beta‐binomial model of detectability that accounts for additional (extra‐binomial) sources of variation in detections among surveys. As an illustration, we fit this model to repeated point counts of the West Indian manatee, which was observed in a pilot study using aerial surveys. Our extension of N ‐mixture models provides increased flexibility. The effects of different sets of covariates may be estimated for the probability of occurrence of a species, for its mean abundance at occupied locations, and for its detectability.

Detecting impairment associated with cannabis with and without alcohol on the Standardized Field Sobriety Tests - Luke A. Downey; Rebecca King; Katherine Papafotiou; Phillip Swann; Edward Ogden; Martin Boorman; Con Stough (Psychopharmacology, 2012)

Assimilating GlobColour ocean colour data into a pre-operational physical-biogeochemical model - D. A. Ford; K. P. Edwards; D. Lea; R. M. Barciela; M. J. Martin; J. Demaria (Ocean Science, 2012)
As part of the GlobColour project, daily chlorophyll a observations, derived using remotely sensed ocean colour data from the MERIS, MODIS and SeaWiFS sensors, are produced. The ability of these products to be assimilated into a pre-operational global coupled physical-biogeochemical model has been tested, on both a hindcast and near-real-time basis, and the impact on the system assessed. The assimilation was found to immediately and considerably improve the bias, root mean square error and correlation of modelled surface chlorophyll concentration compared to the GlobColour observations, an improvement which was sustained throughout the year and in every ocean basin. Errors against independent in situ chlorophyll observations were also reduced, both at and beneath the ocean surface. However, the model fit to in situ observations was not consistently better than that of climatology, due to errors in the underlying model. The assimilation scheme used is multivariate, updating all biogeochemical model state variables at all depths. The other variables were not degraded by the assimilation, with annual mean surface fields of nutrients, alkalinity and carbon variables remaining of similar quality compared to climatology. There was evidence of improved representation of zooplankton concentration, and reduced errors were seen against in situ observations of nitrate and pCO2, but too few observations were available to conclude about global model skill. The near-real-time GlobColour products were found to be sufficiently reliable for operational purposes, and of benefit to both operational-style systems and reanalyses.

Ferumoxytol-Enhanced MRI to Image Inflammation Within Human Brain Arteriovenous Malformations: a Pilot Investigation - David M. Hasan; Matthew Amans; Tarik Tihan; Christopher Hess; Yi Guo; Soonmee Cha; Hua Su; Alastair J. Martin; Michael T. Lawton; Edward A. Neuwelt; David A. Saloner; William L. Young (Translational Stroke Research, 2012)

Estimates of surface drifter trajectories in the equatorial Atlantic: a multi-model ensemble approach - Robert Bruce Scott; Nicolas Ferry; Marie Drévillon; Charlie N. Barron; Nicolas C. Jourdain; Jean-Michel Lellouche; Edward Joseph Metzger; Marie-Hélène Rio; Ole Martin Smedstad (Ocean Dynamics, 2012)

Linking Fine-Scale Sub-Arctic Vegetation Distribution in Complex Topography with Surface-Air-Temperature Modelled at 50-m Resolution - Zhenlin Yang; Martin T. Sykes; Edward Hanna; Terry V. Callaghan (Ambio, 2012)

Metabolic syndrome in mice induced by expressing a transcriptional activator in adipose tissue - Liwen Zhang; Yuchen Zhou; Amber Ying Zhu; Xiang-qing Li; Steven S. Mundt; Ling Gao; JeanMarie Lisnock; Melba Hernandez; Magdalena Alonso-Galicia; Martin S. Springer; Edward A. O’Neill; Bruce L. Daugherty; et al. (Transgenic Research, 2012)

The rate of permafrost carbon release under aerobic and anaerobic conditions and its potential effects on climate - Hanna Lee; Edward A. G. Schuur; Kanika S. Inglett; Martin Lavoie; Jeffrey P. Chanton (Global Change Biology, 2012)
Recent observations suggest that permafrost thaw may create two completely different soil environments: aerobic in relatively well‐drained uplands and anaerobic in poorly drained wetlands. The soil oxygen availability will dictate the rate of permafrost carbon release as carbon dioxide ( CO 2 ) and as methane ( CH 4 ), and the overall effects of these emitted greenhouse gases on climate. The objective of this study was to quantify CO 2 and CH 4 release over a 500‐day period from permafrost soil under aerobic and anaerobic conditions in the laboratory and to compare the potential effects of these emissions on future climate by estimating their relative climate forcing. We used permafrost soils collected from A laska and S iberia with varying organic matter characteristics and simultaneously incubated them under aerobic and anaerobic conditions to determine rates of CO 2 and CH 4 production. Over 500 days of soil incubation at 15 °C, we observed that carbon released under aerobic conditions was 3.9–10.0 times greater than anaerobic conditions. When scaled by greenhouse warming potential to account for differences between CO 2 and CH 4 , relative climate forcing ranged between 1.5 and 7.1. Carbon release in organic soils was nearly 20 times greater than mineral soils on a per gram soil basis, but when compared on a per gram carbon basis, deep permafrost mineral soils showed carbon release rates similar to organic soils for some soil types. This suggests that permafrost carbon may be very labile, but that there are significant differences across soil types depending on the processes that controlled initial permafrost carbon accumulation within a particular landscape. Overall, our study showed that, independent of soil type, permafrost carbon in a relatively aerobic upland ecosystems may have a greater effect on climate when compared with a similar amount of permafrost carbon thawing in an anaerobic environment, despite the release of CH 4 that occurs in anaerobic conditions.

BMP4 loss-of-function mutations in developmental eye disorders including SHORT syndrome - Linda M. Reis; Rebecca C. Tyler; Kala F. Schilter; Omar Abdul-Rahman; Jeffrey W. Innis; Beth A. Kozel; Adele S. Schneider; Tanya M. Bardakjian; Edward J. Lose; Donna M. Martin; Ulrich Broeckel; Elena V. Semina (Human Genetics, 2011)

Survey of 11 nitroimidazole residues in hen and duck eggs from the Irish market - Mark Cronly; Patrice Behan; Barry Foley; Martin Danaher; Edward Malone; Liam Regan (Food Additives & Contaminants Part B-Surveillance, 2011)

Gene identification in black cohosh (Actaea racemosa L.): expressed sequence tag profiling and genetic screening yields candidate genes for production of bioactive secondary metabolites - Martin J. Spiering; Lori A. Urban; Donald L. Nuss; Vivek Gopalan; Arlin Stoltzfus; Edward Eisenstein (Plant Cell Reports, 2011)

Macroscale factors affecting diatom abundance: a synergistic use of Continuous Plankton Recorder and satellite remote sensing data - Dionysios E. Raitsos; Samantha J. Lavender; Christos D. Maravelias; John Haralabous; Abigail McQuatters-Gollop; Martin Edwards; Philip C. Reid (International Journal of Remote Sensing, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Analytical strategy for the determination of non-steroidal anti-inflammatory drugs in plasma and improved analytical strategy for the determination of authorised and non-authorised non-steroidal anti-inflammatory drugs in milk by LC–MS/MS - Geraldine Dowling; Edward Malone; Tom Harbison; Sheila Martin (Food Additives & Contaminants: Part A, 2010)

Conducting Drug Abuse Investigations in Natural Environments: Potential Directions for Medical Toxicology Research - Edward W. Boyer; Richard J. Fay; Aaron Cook; Martin Buckosh; Patricia L. Hibberd; Patricia Case (Journal of Medical Toxicology, 2010)

Evaluation of pathogenicity and aggressiveness of F. langsethiae on oat and wheat seedlings relative to known seedling blight pathogens - Samuel M. Imathiu; Martin C. Hare; Rumiana V. Ray; Matthew Back; Simon G. Edwards (European Journal of Plant Pathology, 2010)

Fractured bedrock and saprolite hydrogeologic controls on groundwater/surface-water interaction: a conceptual model (Australia) - Edward W. Banks; Craig T. Simmons; Andrew J. Love; Roger Cranswick; Adrian D. Werner; Erick A. Bestland; Martin Wood; Tania Wilson (Hydrogeology Journal, 2009)

The effectiveness of a Mesoamerican ‘paper park’ in conserving cloud forest avifauna - Thomas Edward Martin; George Alan Blackburn (Biodiversity and Conservation, 2009)

Growth Hormone Production and Action in N1E-115 Neuroblastoma Cells - Chelsey Grimbly; Brent Martin; Edward Karpinski; Steve Harvey (Journal of Molecular Neuroscience, 2009)

Rapid biogeographical plankton shifts in the North Atlantic Ocean - BEAUGRAND GREGORY; LUCZAK CHRISTOPHE; EDWARDS MARTIN (Global Change Biology, 2009)
Large‐scale biogeographical changes in the biodiversity of a key zooplankton group (calanoid copepods) were detected in the north‐eastern part of the North Atlantic Ocean and its adjacent seas over the period 1960–1999. These findings provided key empirical evidence for climate change impacts on marine ecosystems at the regional to oceanic scale. Since 1999, global temperatures have continued to rise in the region. Here, we extend the analysis to the period 1958–2005 using all calanoid copepod species assemblages (nine species assemblages based on an analysis including a total of 108 calanoid species or taxa) and show that this phenomenon has been reinforced in all regions. Our study reveals that the biodiversity of calanoid copepods are responding quickly to sea surface temperature (SST) rise by moving geographically northward at a rapid rate up to about 23.16 km yr −1 . Our analysis suggests that nearly half of the increase in sea temperature in the northeast Atlantic and adjacent seas is related to global temperature rises (46.35% of the total variance of temperature) while changes in both natural modes of atmospheric and oceanic circulation explain 26.45% of the total variance of temperature. Although some SST isotherms have moved northwards by an average rate of up to 21.75 km yr −1 (e.g. the North Sea), their movement cannot fully quantify all species assemblage shifts. Furthermore, the observed rates of biogeographical movements are far greater than those observed in the terrestrial realm. Here, we discuss the processes that may explain such a discrepancy and suggest that the differences are mainly explained by the fluid nature of the pelagic domain, the life cycle of the zooplankton and the lesser anthropogenic influence (e.g. exploitation, habitat fragmentation) on these organisms. We also hypothesize that despite changes in the path and intensity of the oceanic currents that may modify quickly and greatly pelagic zooplankton species, these organisms may reflect better the current impact of climate warming on ecosystems as terrestrial organisms are likely to significantly lag the current impact of climate change.

Monitoring Benthic AIgal Communides:A Comparison of Targeted and Coefficient Sampling Methods - Matthew S. Edwards; Martin T. Tinker (Algae, 2009)

Fusarium langsethiae pathogenicity and aggressiveness towards oats and wheat in wounded and unwounded in vitro detached leaf assays - Samuel M. Imathiu; Rumiana V. Ray; Matthew Back; Martin C. Hare; Simon G. Edwards (European Journal of Plant Pathology, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Reply to Haddock, S.H.D. Reconsidering evidence for potential climate‐related increases in jellyfish - Martin J. Attrill; Martin Edwards (Limnology and Oceanography, 2008)

Causes and projections of abrupt climate‐driven ecosystem shifts in the North Atlantic - Grégory Beaugrand; Martin Edwards; Keith Brander; Christophe Luczak; Frederic Ibanez (Ecology Letters, 2008)
Warming of the global climate is now unequivocal and its impact on Earth’ functional units has become more apparent. Here, we show that marine ecosystems are not equally sensitive to climate change and reveal a critical thermal boundary where a small increase in temperature triggers abrupt ecosystem shifts seen across multiple trophic levels. This large‐scale boundary is located in regions where abrupt ecosystem shifts have been reported in the North Atlantic sector and thereby allows us to link these shifts by a global common phenomenon. We show that these changes alter the biodiversity and carrying capacity of ecosystems and may, combined with fishing, precipitate the reduction of some stocks of Atlantic cod already severely impacted by exploitation. These findings offer a way to anticipate major ecosystem changes and to propose adaptive strategies for marine exploited resources such as cod in order to minimize social and economic consequences.

A new African streak virus species from Nigeria - Sunday Oluwafemi; Arvind Varsani; Adérito L. Monjane; Dionne N. Shepherd; Betty E. Owor; Edward P. Rybicki; Darren P. Martin (Archives of Virology, 2008)

Aureoles of Pb(II)-enriched feldspar around monazite in paragneiss and anatectic pods of the Napier Complex, Enderby Land, East Antarctica: the roles of dissolution-reprecipitation and diffusion - Edward S. Grew; Martin G. Yates; Christopher J. L. Wilson (Contributions to Mineralogy and Petrology, 2008)

Pyrethroid tolerance is associated with elevated expression of antioxidants and agricultural practice in Anopheles arabiensis sampled from an area of cotton fields in Northern Cameroon - PIE MÜLLER; MOUHAMADOU CHOUAÏBOU; PATRICIA PIGNATELLI; JOSIANE ETANG; EDWARD D. WALKER; MARTIN J. DONNELLY; FRÉDÉRIC SIMARD; HILARY RANSON (Molecular Ecology, 2008)
Spraying of agricultural crops with insecticides can select for resistance in nontarget insects and this may compromise the use of insecticides for the control of vector‐borne diseases. The tolerance of the malaria vector, Anopheles arabiensis to deltamethrin was determined in a field population from a cotton‐growing region of Northern Cameroon both prior to and midway through the 4‐month period of insecticide application to the cotton crop. A 1.6‐fold increase in the median knockdown time was observed. To determine whether this increased tolerance was associated with constitutively elevated levels of genes commonly associated with insecticide resistance, RNA was extracted from F 1 progeny from family lines of field‐caught mosquitoes and hybridized to the Anopheles gambiae detox chip. The experimental design avoided the confounding effects of colonization, and this study is the first to measure gene expression in the progeny of gravid, wild‐caught mosquitoes. Several genes with antioxidant roles, including superoxide dismutases, a glutathione S‐transferase and a thioredoxin‐dependent peroxidase, and a cytochrome P450 showed elevated expression in mosquito families collected during the insecticide‐spraying programme. These genes may constitute an important general defence mechanism against insecticides. Intriguingly, the levels of expression of these genes were strongly correlated suggesting a common regulatory mechanism.

A biological consequence of reducing Arctic ice cover: arrival of the Pacific diatom Neodenticula seminae in the North Atlantic for the first time in 800 000 years - PHILIP C. REID; DAVID G. JOHNS; MARTIN EDWARDS; MICHEL STARR; MICHEL POULIN; PAULI SNOEIJS (Global Change Biology, 2007)
The Continuous Plankton Recorder survey has monitored plankton in the Northwest Atlantic at monthly intervals since 1962, with an interegnum between 1978 and 1990. In May 1999, large numbers of the Pacific diatom Neodenticula seminae were found in Continuous Plankton Recorder (CPR) samples in the Labrador Sea as the first record in the North Atlantic for more than 800 000 years. The event coincided with modifications in Arctic hydrography and circulation, increased flows of Pacific water into the Northwest Atlantic and in the previous year the exceptional occurrence of extensive ice‐free water to the North of Canada. These observations indicate that N. seminae was carried in a pulse of Pacific water in 1998/early 1999 via the Canadian Arctic Archipelago and/or Fram Strait. The species occurred previously in the North Atlantic during the Pleistocene from∼1.2 to∼0.8 Ma as recorded in deep sea sediment cores. The reappearance of N. seminae in the North Atlantic is an indicator of the scale and speed of changes that are taking place in the Arctic and North Atlantic oceans as a consequence of regional climate warming. Because of the unusual nature of the event it appears that a threshold has been passed, marking a change in the circulation between the North Pacific and North Atlantic Oceans via the Arctic. Trans‐Arctic migrations from the Pacific into the Atlantic are likely to occur increasingly over the next 100 years as Arctic ice continues to melt affecting Atlantic biodiversity and the biological pump with consequent feedbacks to the carbon cycle.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

FDG-PET for Pharmacodynamic Assessment of the Fatty Acid Synthase Inhibitor C75 in an Experimental Model of Lung Cancer - Jae Sung Lee; Hajime Orita; Kathleen Gabrielson; Sara Alvey; Ruth L. Hagemann; Francis P. Kuhajda; Edward Gabrielson; Martin G. Pomper (Pharmaceutical Research, 2007)

A long‐term chlorophyll dataset reveals regime shift in North Sea phytoplankton biomass unconnected to nutrient levels - Abigail McQuatters-Gollop; Dionysios E. Raitsos; Martin Edwards; Yaswant Pradhan; Laurence D. Mee; Samantha J. Lavender; Martin J. Attrill (Limnology and Oceanography, 2007)
During the 1980s, a rapid increase in the Phytoplankton Colour Index (PCI), a semiquantitative visual estimate of algal biomass, was observed in the North Sea as part of a regionwide regime shift. Two new data sets created from the relationship between the PCI and SeaWiFS chlorophyll a (Chl a ) quantify differences in the previous and current regimes for both the anthropogenically affected coastal North Sea and the comparatively unaffected open North Sea. The new regime maintains a 13% higher Chl a concentration in the open North Sea and a 21% higher concentration in coastal North Sea waters. However, the current regime has lower total nitrogen and total phosphorus concentrations than the previous regime, although the molar N: P ratio in coastal waters is now well above the Redfield ratio and continually increasing. Besides becoming warmer, North Sea waters are also becoming clearer (i.e., less turbid), thereby allowing the normally light‐limited coastal phytoplankton to more effectively utilize lower concentrations of nutrients. Linear regression analyses indicate that winter Secchi depth and sea surface temperature are the most important predictors of coastal Chl a , while Atlantic inflow is the best predictor of open Chl a ; nutrient concentrations are not a significant predictor in either model. Thus, despite decreasing nutrient concentrations, Chl a continues to increase, suggesting that climatic variability and water transparency may be more important than nutrient concentrations to phytoplankton production at the scale of this study.

Climate‐related increases in jellyfish frequency suggest a more gelatinous future for the North Sea - Martin J. Attrill; Jade Wright; Martin Edwards (Limnology and Oceanography, 2007)
Data obtained since 1958 from the continuous plankton recorder show an increasing occurrence of jellyfish in the central North Sea that is positively related to the North Atlantic Oscillation (NAO) and Atlantic inflow to the northern North Sea. Since 1970, jellyfish frequency has been also significantly negatively correlated with mean annual pH, independent of NAO trends. Jellyfish frequency increased in the mid‐1980s, coincident with the reported regime shift in the North Sea and tracking trends in phytoplankton color. As models produced under all climate‐change scenarios indicate a move toward a positive NAO, and pH of the oceans is predicted to decrease with rising CO 2 , we suggest that jellyfish frequency will increase over the next 100 yr.

Movement kinematics in prehension are affected by grasping objects of different mass - Daniel Eastough; Martin G. Edwards (Experimental Brain Research, 2006)

The Absorption of Darbepoetin Alfa Occurs Predominantly via the Lymphatics Following Subcutaneous Administration to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Anne C. Heatherington; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2006)

Phosphorus Translocation by Red Deer on a Subalpine Grassland in the Central European Alps - Martin Schütz; Anita C. Risch; Gérald Achermann; Conny Thiel-Egenter; Deborah S. Page-Dumroese; Martin F. Jurgensen; Peter J. Edwards (Ecosystems, 2006)

Electrophysiological correlates of neural plasticity compensating for ischemia-induced damage in the hippocampus - Sabrina Wang; Nohjin Kee; Edward Preston; J. Martin Wojtowicz (Experimental Brain Research, 2005)

Nicotine physical dependence and tolerance in the mouse following chronic oral administration - Sheri D. Grabus; Billy R. Martin; Angela M. Batman; Rachel F. Tyndale; Edward Sellers; M. Imad Damaj (Psychopharmacology, 2005)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

GROWTH, IMMORTALIZATION, AND DIFFERENTIATION POTENTIAL OF NORMAL ADULT HUMAN PROXIMAL TUBULE CELLS - DAVID E. OROSZ; PHILIP G. WOOST; ROBERT J. KOLB; MARGARET B. FINESILVER; WENWU JIN; PHYLLIS S. FRISA; CHEE-KEONG CHOO; CHUNG-FAI YAU; KWOK-WAH CHAN; MARTIN I. RESNICK; JANICE G. DOUGLAS; JOHN C. EDWARDS; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Growth, immortalization, and differentiation potential of normal adult human proximal tubule cells - David Orosz; Martin Resnick; Jurgen Wehland; Janice Douglas; John Edwards; James Jacobberger; Ulrich Hopfer; Philip Woost; Robert Kolb; Margaret Finesilver; Wenwu Jin; Phyllis Frisa; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Strategies for the Control of Fusarium Head Blight in Cereals - Stoyan R. Pirgozliev; Simon G. Edwards; Martin C. Hare; Peter Jenkinson (European Journal of Plant Pathology, 2003)

Periodic changes in the zooplankton of the North Sea during the twentieth century linked to oceanic inflow - Philip C. Reid; Martin Edwards; Gregory Beaugrand; Morten Skogen; Darren Stevens (Fisheries Oceanography, 2003)
Oceanic inflow is estimated to contribute more than 90% of the nutrient input into the North Sea. Variability in the volume, chemical properties, biological content and source of the inflowing water is thus likely to have a considerable effect on North Sea ecosystems. Changes seen in the plankton, and in particular Calanus finmarchicus and Calanus helgolandicus , over the last 40 years as measured by the Continuous Plankton Recorder survey, allow clear periods to be identified that appear to be associated with variability in inflow. Monthly estimates of inflow and outflow across a section between Orkney and Utsira in Norway as well as netflow (sum of Baltic outflow, runoff and Channel inflow), have been derived from runs of the NORWECOM model for two integrated depth intervals: surface to 150 m and >150 m. A comparison is made between the physical model output and plankton results for the period 1958–99. Distinct plankton periods that appear to reflect changing inflow events are discussed in relation to hydrometeorological and earlier plankton studies over approximately the last 100 years.

Pharmacokinetic Model to Describe the Lymphatic Absorption of r-metHu-Leptin After Subcutaneous Injection to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Maria Brumm; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2003)

Characterization of expressed pigmented core light harvesting complex (LH 1) in a reaction center deficient mutant of Blastochloris viridis - Agnes E. Ostafin; Nina S. Ponomarenko; Julia A. Popova; Martin Jäger; Edward J. Bylina; James R. Norris (Photosynthesis Research, 2003)

Seminested PCR for the detection and analysis of flue-cured tobacco (Nicotiana tabacum) expressing a chitinase transgene - Jiao Shi; Martin Naylor; Mary-Lou Edwards; Jin Feng Han; Ian Cooper (Plant Molecular Biology Reporter, 2002)

Estimating recharge at Yucca Mountain, Nevada, USA: comparison of methods - Alan L. Flint; Lorraine E. Flint; Edward M. Kwicklis; June T. Fabryka-Martin; Gudmundur S. Bodvarsson (Hydrogeology Journal, 2002)

1H NMR investigations of the molecular nature of low-molecular-mass calcium ions in biofluids - Christopher J. Silwood; Martin Grootveld; Edward Lynch (JBIC Journal of Biological Inorganic Chemistry, 2002)

Cumulative exposure to tamoxifen: DNA adducts and liver cancer in the rat - Philip Carthew; Peter Lee; Richard Edwards; Robert Heydon; Barbara Nolan; Elizabeth Martin (Archives of Toxicology, 2001)

The CD4 T cell-deficient mouse mutation nackt ( nkt ) involves a deletion in the cathepsin L ( Ctsl ) gene - Fernando Benavides; Ann Venables; Heather Poetschke Klug; Edward Glasscock; Natalia Martin Palenzuela; Claudio J. Conti; Alexander Rudensky; Marcela Gmez; Jean-Louis Gunet; Ellen R. Richie (Immunogenetics, 2001)

Surface pollen‐vegetation relationships on the Atlantic seaboard: South Uist, Scotland - Barbara A. Brayshay; David D. Gilbertson; Martin Kent*; Kevin J. Edwards; Peter Wathern; Ruth E. Weaver (Journal of Biogeography, 2000)
Studies of modern pollen rain from remote islands have raised a number of interesting issues concerning the spatial precision of present‐day pollen spectra in relation to their parent plant community types. This paper examines the relationships and degree of correlation between a sequence of contemporary vegetation types, environments and their associated surface pollen spectra from a transect across the island of South Uist in the Outer Hebrides of Scotland. Paired data on both contemporary vegetation and associated surface pollen assemblages have been collected and analysed using methods of numerical classification and ordination. In general terms, the modern pollen rain on South Uist reflects the major changes in vegetation pattern and the major community types fairly closely. The major boundary between the alkaline machair sand dune communities and the various acidic upland vegetation types is particularly clear. However, both variability in the vegetation and the effects of the strong prevailing westerly and south‐westerly winds tend to blur the boundaries of the various communities within each of these larger categories. On average 86.6% of the palynomorphs come from in‐community quadrat sources, while only 1.3% are from off‐island sources. The limited present‐day tree distribution on the transect is discussed in the context of the more widespread distribution of arboreal pollen. Overall, there is a strong numerical correspondence between vegetation, pollen and environmental variables. The various problems inherent in examining surface pollen spectra are reviewed.

Zebra mussel filter feeding and food-limited production of Daphnia: recent changes in lower trophic level dynamics of Oneida Lake, New York, U.S.A. - Martin J. Horgan; Edward L. Mills (Hydrobiologia, 1999)

An example of intron junctional sliding in the gene families encoding squalene monooxygenase homologues in Arabidopsis thaliana and Brassica napus* - Ulrike A. Schäfer; Darwin W. Reed; David G. Hunter; Kening Yao; Alan M. Weninger; Edward W.T. Tsang; Martin J.T. Reaney; Samuel L. MacKenzie; Patrick S. Covello (Plant Molecular Biology, 1999)

Is observed variability in the long‐term results of the Continuous Plankton Recorder survey a response to climate change? - PHILIP C. REID; BENJAMIN PLANQUE; MARTIN EDWARDS (Fisheries Oceanography, 1998)
In the more than 50 years that the Continuous Plankton Recorder (CPR) survey has operated on a regular monthly basis in the north‐east Atlantic and North Sea, large changes have been witnessed in the planktonic ecosystem. These changes have taken the form of long‐term trends in abundance for certain species or stepwise changes for others, and in many cases are correlated with a mode of climatic variability in the North Atlantic, either: (1) the North Atlantic Oscillation (NAO), a basin‐scale atmospheric alteration of the pressure field between the Azores high pressure cell and the Icelandic Low; or (2) the Gulf Stream Index (GSI), which measures the latitudinal position of the north wall of the Gulf Stream. Recent work has shown that the changes in the GSI are coupled with the NAO and Pacific Southern Oscillation with a 2 year lag. The plankton variability is also possibly linked to changes observed in the distribution and flux of water masses in the surface, intermediate and deep waters of the North Atlantic. For example, in the last two decades, the extent and location of the formation of North Atlantic Deep Water, Labrador Sea Intermediate Water and Norwegian Sea intermediate and upper‐layer water has altered considerably. This paper discusses the extent to which observed changes in plankton abundance and distribution may be linked to this basin‐scale variability in hydrodynamics. The results are also placed within the context of global climate warming and the possible effects of the observed melting of Arctic permafrost and sea ice on the subpolar North Atlantic.

Kornerupine parageneses in whiteschists and other magnesian rocks: is kornerupine + talc a high-pressure assemblage equivalent to tourmaline + orthoamphibole? - Edward S. Grew; Nikolai N. Pertsev; Stanislav Vrána; Martin G. Yates; Charles K. Shearer; Michael Wiedenbeck (Contributions to Mineralogy and Petrology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Cellular changes and physiological responses to tuber pressure-bruising - Edward C. Lulai; Martin T. Glynn; Paul H. Orr (American Journal of Potato Research, 1996)